Fiber treatment composition for cosmetic composition or head article
By combining cationic polymers with anionic polymers of specific viscosities to form cross-linked polyionic complexes, the shortcomings of existing cosmetic compositions in terms of hair texture, moisture resistance, and stability are solved, achieving high-quality, moisture-resistant, and stable hair treatment effects.
Patent Information
- Application Number
- CN202380042539.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-23
- Filing Date
- 2023-05-26
- Publication Date
- 2025-01-07
AI Technical Summary
Existing cosmetic compositions containing cationic and anionic polymers are not effective in improving hair texture and moisture resistance, and lack stability, especially in high humidity conditions where they tend to become frizzy and have poor washability.
A cationic polymer of a specific viscosity is combined with anionic polymers, and modified silicone and dimethyl polysiloxane are added to form a polyionic complex. Through ionic interactions, a cross-linked structure is formed to create a hydrophobic film to improve texture and moisture resistance. Cationic surfactants and higher alcohols are added to improve stability.
It significantly improves the texture and moisture resistance of hair or headwear products, inhibits tangling and frizz, and maintains its effect under high humidity conditions with high stability.
Smart Images

Figure BDA0005150277210000081 
Figure BDA0005150277210000161 
Figure BDA0005150277210000351
Abstract
Description
Technical Field
[0001] The present invention relates to a cosmetic composition or a fiber treatment composition for a headdress product. Background Art
[0002] Aqueous compositions for treating keratinous substances containing cationic polymers and anionic polymers are known. For example, Japanese Patent Application Laid-Open No. 53-139734 (Patent Document 1) describes that by using a composition for treating keratinous substances characterized by containing at least one anionic polymer and at least one cationic polymer in a solvent medium, anionic polymers can be fixed to keratinous substances, which may include hair, skin or nails in particular. In addition, as a reason for obtaining the above-mentioned effect, it is assumed that it is related to the complex formed by the interaction between the anionic polymer and the cationic polymer.
[0003] Regarding hair cosmetics containing a cationic polymer and an anionic polymer, for example, Japanese Patent Application Laid-Open No. 2008-297295 (Patent Document 2) discloses a hair treatment composition containing (A) L-theanine and (B) a nonionic polymer, an amphoteric polymer, and a cationic polymer as a polymer compound, and states that an anionic polymer may be contained as required. In addition, it is disclosed that the hair treatment composition can impart softness to hair and improve the elasticity of the hair root vicinity.
[0004] Japanese Patent Application Laid-Open No. 2005-166333 (Patent Document 3) describes that a hair cosmetic containing a cationic polymer having a charge density within a specific range and an anionic polymer containing 80% by mass or more and 100% by mass or less of a specific anionic structural unit and having a weight average molecular weight of 4,000 or more and 80,000 or less can improve the touch and appearance of damaged hair, and these effects can be sustained even after repeated shampooing. Summary of the invention
[0005] The present invention relates to a cosmetic composition or a fiber treatment composition for a headdress product, comprising: (A) a cationic polymer having a viscosity of 1,000 mPa·s or more in a 1 mass % aqueous solution at 30° C., (B) an anionic polymer, (C) one or more modified silicones selected from silicones modified with hydroxy groups at both ends, polyglycerol-modified silicones, amino-modified silicones, aminopolyether-modified silicones, and polyether-modified silicones, (D) dimethylpolysiloxane, (E) a cationic surfactant, and (F) a higher alcohol, wherein the mass ratio of the component (A) to the component (B) [(A) / (B)] is 4.5 or more. DETAILED DESCRIPTION
[0006] As described in Patent Document 1, it is known that a composition containing a complex formed of a cationic polymer and an anionic polymer (hereinafter also referred to as a "polyion complex") is used as a composition for treating keratin substances such as hair, but there is still room for improvement in terms of improving its performance. For example, in a conditioner, which is a type of hair cosmetic composition, it is required to improve the texture of the treated hair, suppress tangling, and have excellent moisture resistance without being tangled under high humidity conditions. However, no particular effect can be obtained in the prior art of Patent Documents 1 to 3. In addition, the treatment effect of hair may be lost after one shampooing, and it is expected to improve the sustainability of the treatment effect (washing resistance).
[0007] Furthermore, compositions containing polyion complexes are sometimes in the form of oil-in-water or water-in-oil emulsion compositions, but in these emulsion compositions, improvement of stability over time is a problem. In particular, in hair cosmetic compositions, cationic surfactants, higher alcohols, etc. are sometimes added to improve the touch of treated hair. However, there is a problem that when these components are added to a composition containing a polyion complex, stability is easily reduced.
[0008] The present invention relates to providing a cosmetic composition or a fiber treatment composition for a headdress product which can improve the texture-enhancing effect of a treated object, the sustainability of the effect, and moisture resistance and has high stability.
[0009] The present inventors have found that the above-mentioned problems can be solved by a composition containing a cationic polymer having a 1 mass % aqueous solution viscosity of a specific value or more, an anionic polymer, a specific silicone compound, and water.
[0010] According to the present invention, there can be provided a cosmetic composition or a fiber treatment composition for hair products that can improve the texture-enhancing effect of a treated object and the sustainability of the effect, as well as moisture resistance, and, particularly when used for treating hair or fibers for hair products, can improve the tangling-inhibiting effect of hair or fibers for hair products and the sustainability of the effect, can suppress the tangling of hair under high humidity conditions, and has high stability.
[0011] [Cosmetic composition or fiber treatment composition for headdress products]
[0012] The cosmetic composition or fiber treatment composition for headwear products of the present invention (hereinafter, also referred to as the "composition of the present invention") contains (A) a cationic polymer having a viscosity of 1% by mass aqueous solution at 30°C of 1,000 mPa·s or more, (B) an anionic polymer, (C) one or more modified silicones selected from polyglycerol-modified silicone and amino-modified silicone, (D) dimethyl polysiloxane, (E) a cationic surfactant, and (F) a higher alcohol, wherein the mass ratio of the component (A) to the component (B) [(A) / (B)] is 4.5 or more.
[0013] In addition, in this specification, "containing component X" also includes compounding component X.
[0014] The composition of the present invention has the above-mentioned structure, and can improve the texture improvement effect of the treated object and the sustainability of the effect, as well as the moisture resistance. In particular, when used for treating hair or fibers for hair accessories, the composition can improve the hair tangling prevention effect and the sustainability of the effect, and can prevent the hair from becoming tangled under high humidity conditions, and has high stability.
[0015] The reason why the composition of the present invention achieves the above-mentioned effects is not certain, but is considered as follows.
[0016] The composition of the present invention comprises a polyion complex formed by a component (A) and a component (B) in a specific ratio. It is believed that in the polyion complex, a cross-linked structure is formed between the component (A) and the component (B) by ionic interaction, and thus, the film obtained by using the composition of the present invention exhibits a higher elastic modulus. Further, the polyion complex is poorly soluble in water, and a hydrophobic film can be formed by applying the composition comprising the polyion complex to an object. It is believed that by forming the hydrophobic film, the texture and moisture resistance of the object to be treated are improved.
[0017] The viscosity of a 1% by mass aqueous solution of the component (A) used in the present invention at 30°C is 1,000 mPa·s or more. It is believed that by using the component (A), the lubricity of the obtained film is improved, and thus the texture of the treated object is further improved. When the composition of the present invention is used for treating hair or fibers for hair accessories, the effect of inhibiting the tangling of the fibers for hair accessories is improved. In addition, the polyion complex containing the component (A) has high stability. Therefore, even when an oily component such as the component (E) or (F) is added to form an emulsified composition, the structure of the polyion complex is not easily destroyed, thereby improving the stability.
[0018] Furthermore, the composition of the present invention contains silicone compounds as components (C) and (D). The modified silicone as component (C) has high adsorption to keratin substances, and component (D) is a compound with high hydrophobicity and low surface tension. Therefore, it is believed that if the composition of the present invention is applied to a treatment object, the surface of the object is hydrophobically coated with components (C) and (D), and the texture improvement effect of the treatment object, the sustainability of the effect, and moisture resistance are further improved.
[0019] The composition of the present invention is preferably a cosmetic composition for keratin substances such as skin, hair, eyelashes, eyebrows, and nails, or a fiber treatment composition for hair products, more preferably a cosmetic composition for skin or hair, and a fiber treatment composition for hair products, further preferably a cosmetic composition for skin or hair, and even more preferably a hair cosmetic composition.
[0020] Among cosmetic compositions, examples of product forms of skin cosmetic compositions include body wash, facial cleanser, bath preparation, deodorant preparation, makeup, sunscreen, primer, emulsion, beauty serum, and cream.
[0021] In addition, examples of product forms of the hair cosmetic composition include shampoo, hair essence, hair conditioner, hair treatment (including leave-in), hair setting agent, hair dye, hair perm, etc. Among these, hair conditioner, hair treatment or hair setting agent is preferred from the viewpoint of effectiveness of the effect of the present invention.
[0022] As the fiber for headdress products that becomes the application object of the composition of the present invention, it can be any one of natural fiber and synthetic fiber, but preferably natural fiber. Fibers derived from nature refer to fibers collected from natural animals and plants, or fibers artificially manufactured using collagen, casein, soybeans, peanuts, corn, silk scraps, fibroin, etc. as raw materials, and fibers for headdress products. Among these, preferably, fibers artificially manufactured using collagen, casein, soybeans, peanuts, corn, silk scraps, fibroin, etc. as raw materials, more preferably regenerated collagen fibers using collagen as raw materials, regenerated protein fibers such as regenerated silk fibers using fibroin as raw materials, and more preferably regenerated collagen fibers.
[0023] Regenerated collagen fibers can be produced by known techniques. The composition of regenerated collagen fibers does not need to be 100% collagen, and may contain natural polymers, synthetic polymers, additives, etc. for quality improvement. Furthermore, regenerated collagen fibers may be post-processed fibers.
[0024] As the form of the regenerated collagen fiber, filaments are preferably used. The filaments are generally taken out from a reel or a box. In addition, in the production process of the regenerated collagen fiber, the filaments obtained from the drying process can also be directly used.
[0025] As synthetic fibers, fibers containing synthetic resins as main components can be cited. From the viewpoint of ease of manufacturing of synthetic fibers and the viewpoint of obtaining a texture close to that of hair, the synthetic resin is preferably a thermoplastic resin, and more preferably one or more selected from polyester resins, polyamide resins, polyimide resins, polyamideimide resins, vinyl chloride resins, polycarbonate resins, polyphenylene sulfide resins, and modified polyacrylonitrile resins (modacrylic resins) (copolymers of acrylonitrile and vinyl chloride). The "main component" mentioned here refers to a component whose content in the synthetic fiber is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, further more preferably 80% by mass or more, further more preferably 90% by mass or more and 100% by mass or less.
[0026] The synthetic fiber may further contain various agents such as flame retardants, flame retardant aids, light or heat stabilizers, fluorescent agents, antioxidants, antistatic agents, ultraviolet absorbers, etc. in addition to the above-mentioned synthetic resins within a range not impairing the effects of the present invention.
[0027] The form of the composition of the present invention is preferably an emulsified composition, and is more preferably an oil-in-water emulsified composition from the viewpoint of improving the stability of the composition and the viewpoint of improving the feeling during use.
[0028] Hereinafter, each component contained in the composition of the present invention will be described.
[0029] (Component (A): cationic polymer)
[0030] Component (A) is a cationic polymer having a viscosity of 1,000 mPa·s or more in a 1 mass % aqueous solution at 30° C., and is a polymer that can form a polyion complex through interaction with component (B).
[0031] The cationic polymer as component (A) is preferably a polymer having a cationic group and having a positive charge as a total charge. Component (A) may also have an anionic group, a nonionic group, or an amphoteric group such as a betaine group in addition to the cationic group within the range that does not impair the effects of the present invention.
[0032] In the present specification, the cationic group is a cationic group or a group that can become a cationic group by ionization, and specific examples thereof include a primary amino group, a secondary amino group, a tertiary amino group, and a quaternary ammonium group.
[0033] The anionic group is an anionic group or a group that can be ionized to become an anionic group. Specifically, one or more of acidic groups such as carboxyl, sulfonic acid, and phosphoric acid can be cited, preferably one or more of carboxyl and sulfonic acid, more preferably carboxyl. At least a portion of the anionic group can also be neutralized to form a salt.
[0034] From the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and its sustainability, improving moisture resistance, and improving the stability of the composition, the viscosity of a 1 mass % aqueous solution of component (A) at 30° C. is 1,000 mPa·s or more, preferably 1,300 mPa·s or more, more preferably 1,500 mPa·s or more, further preferably 1,700 mPa·s or more, and further more preferably 1,800 mPa·s or more. The upper limit of the viscosity is not particularly limited, but from the viewpoint of the ease of forming the polyion complex and the handleability, it is preferably 100,000 mPa·s or less, more preferably 80,000 mPa·s or less, further preferably 50,000 mPa·s or less, further more preferably 30,000 mPa·s or less, and further more preferably 25,000 mPa·s or less. Furthermore, the viscosity of a 1 mass % aqueous solution of component (A) at 30° C. is 1,000 mPa·s or more, preferably 1,000 mPa·s or more and 100,000 mPa·s or less, more preferably 1,300 mPa·s or more and 80,000 mPa·s or less, further preferably 1,500 mPa·s or more and 50,000 mPa·s or less, further more preferably 1,700 mPa·s or more and 30,000 mPa·s or less, and further more preferably 1,800 mPa·s or more and 25,000 mPa·s or less.
[0035] Specifically, the viscosity of a 1 mass % aqueous solution of the component (A) at 30° C. can be measured by the method described in the Examples.
[0036] The cationic charge density of component (A) is preferably 0.1 mmol / g or more, more preferably 0.2 mmol / g or more, further preferably 0.3 mmol / g or more, and further preferably 0.5 mmol / g or more, from the viewpoint of facilitating the formation of a polyion complex by interaction with component (B), improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of hair or fibers for hair ornament products when used for treating hair or fibers for hair ornament products and the sustainability of the effect, improving moisture resistance, and improving the stability of the composition. In addition, from the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and its sustainability, improving the moisture resistance, and improving the stability of the composition, it is preferably 20 mmol / g or less, more preferably 15 mmol / g or less, further preferably 12 mmol / g or less, further more preferably 10 mmol / g or less, further more preferably 7.0 mmol / g or less, and further more preferably 5.0 mmol / g or less. In addition, the cationic charge density of component (A) is preferably 0.1 mmol / g or more and 20 mmol / g or less, more preferably 0.2 mmol / g or more and 15 mmol / g or less, 0.2 mmol / g or more and 12 mmol / g or less, further more preferably 0.3 mmol / g or more and 10 mmol / g or less, further more preferably 0.3 mmol / g or more and 7.0 mmol / g or less, and further more preferably 0.5 mmol / g or more and 5.0 mmol / g or less.
[0037] The cationic charge density of component (A) is the molar number of cationic groups contained per 1 g of polymer. Furthermore, when at least a part of the cationic groups of component (A) are in the form of neutralized salts, the molar number of cationic groups also includes the molar number of cationic groups in the form of salts.
[0038] In addition, as component (A), two or more polymers may be used. In this case, the cationic charge density of component (A) is determined by calculating a weighted average from the cationic charge density and the blending amount of each polymer.
[0039] As the component (A), any of natural polymers such as cationized polysaccharides or cationized products thereof, and synthetic polymers can be used. However, synthetic polymers are preferred from the viewpoint of easy availability.
[0040] Specific examples of the polymer used as component (A) include cationized polyvinyl alcohol having a viscosity of 1% by mass aqueous solution at 30° C. of 1,000 mPa·s or more, polyethyleneimine, methacryloylethyltrimethylammonium salt polymer, quaternized dialkylaminoalkyl (meth)acrylate polymer, diallylquaternary ammonium salt polymer, methacrylamidepropyltrimethylammonium salt polymer, vinylimidazolium trichloride-vinylpyrrolidone copolymer (polyquaternium-16), vinylpyrrolidone-(meth)acrylic acid alkylamino ester copolymer, vinylpyrrolidone-(meth)acrylic acid alkylamino ester-vinylcaprolactam copolymer, alkylacrylamide-(meth)acrylate-alkylaminoalkylacrylamide-polyethylene glycol (meth)acrylate copolymer, adipic acid-dimethylaminohydroxypropylethylenetriamine copolymer, and the like, and one or more of these can be used. In addition, in the present specification, "(meth)acrylic acid" means acrylic acid or methacrylic acid, and "(meth)acrylate" means acrylic acid or methacrylate.
[0041] Among the above, examples of the methacryloylethyltrimethylammonium salt polymer include methacryloylethyltrimethylammonium chloride polymer (Polyquaternium-37), methacryloylethyldimethylbetaine-methacryloylethyltrimethylammonium chloride-methoxypolyethylene glycol methacrylate copolymer (Polyquaternium-49), and methacryloylethyldimethylbetaine-methacryloylethyltrimethylammonium chloride-2-hydroxyethyl methacrylate copolymer (Polyquaternium-48).
[0042] Examples of the quaternized dialkylaminoalkyl (meth)acrylate polymer include vinyl pyrrolidone-N,N-dimethylaminoethyl diethyl methacrylate sulfate copolymer (polyquaternium-11), N,N-dimethylaminoethyl diethyl methacrylate sulfate-N,N-dimethylacrylamide-polyethylene glycol dimethacrylate copolymer (polyquaternium-52), and the like.
[0043] Examples of the diallyl quaternary ammonium salt polymer include dimethyldiallylammonium chloride polymer (polyquaternium-6), dimethyldiallylammonium chloride-acrylic acid copolymer (polyquaternium-22), dimethyldiallylammonium chloride-acrylamide copolymer (polyquaternium-7), and acrylamide-acrylic acid-dimethyldiallylammonium chloride copolymer (polyquaternium-39).
[0044] In addition, examples of the methacrylamide propyl trimethylammonium salt polymer include methacrylamide propyl trimethylammonium chloride polymer, vinyl pyrrolidone-methacrylamide propyl trimethylammonium chloride copolymer, acrylic acid-methyl acrylate-methacrylamide propyl trimethylammonium chloride copolymer (polyquaternium-47), acrylic acid-acrylamide-methacrylamide propyl trimethylammonium chloride copolymer (polyquaternium-53), and the like.
[0045] From the viewpoint of improving the film-forming ability, improving the texture-improving effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of hair or fibers for hair ornament products when used for treating hair or fibers for hair ornament products and the sustainability of the effect, and improving moisture resistance, component (A) is preferably a polymer containing a structural unit represented by the following general formula (1).
[0046]
[0047] In formula (1), R 1 is a hydrogen atom or a methyl group, R 2 ~R 4 Each independently represents an alkyl group having 1 to 4 carbon atoms. X represents -O- or -NH-, and m represents a number of 1 to 4.
[0048] R in the general formula (1) 1 Preferably, methyl, R 2 ~R 4 Each independently is preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group or an ethyl group, and still more preferably a methyl group.
[0049] In the general formula (1), X is preferably -O-, and m is preferably 1 or more and 3 or less, and more preferably 2 or more and 3 or less.
[0050] Examples of the structural unit represented by the general formula (1) include one or more structural units derived from methacryloylethyltrimethylammonium salt, structural units derived from N,N-dimethylaminoethyl diethyl methacrylate sulfate, and structural units derived from methacrylamidopropyltrimethylammonium salt, and preferably one or more structural units derived from methacryloylethyltrimethylammonium salt and structural units derived from N,N-dimethylaminoethyl diethyl methacrylate sulfate.
[0051] Component (A) may also be a polymer containing other structural units other than the structural unit represented by the general formula (1). Examples of the other structural units include structural units derived from vinyl monomers such as vinyl pyrrolidone, amphoteric monomers such as (meth)acryloylethyl dimethyl betaine, alkyl (meth)acrylates, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, and acrylamides such as N,N-dimethylacrylamide. In addition, component (A) may also be a cross-linked polymer cross-linked by polyethylene glycol di(meth)acrylate or the like.
[0052] In component (A), from the viewpoint of improving film-forming ability, improving the texture-improving effect of the treated object and the sustainability of the effect, and improving the tangling-inhibiting effect of hair or fibers for hair ornament products, especially when used for treating hair or fibers for hair ornament products, and the sustainability of the effect, the content of the structural unit represented by the general formula (1) is preferably 8.0 mol% or more, more preferably 10 mol% or more, and 100 mol% or less, based on the total structural units constituting component (A).
[0053] Component (A) can be used alone or in combination of two or more. Among the above, component (A) is preferably one or more selected from methacryloylethyltrimethylammonium salt polymers and quaternary dialkylaminoalkyl (meth)acrylate polymers, and more preferably methacryloylethyltrimethylammonium chloride polymers (polyquaternium-37), methacryloylethyldimethylbetaine-methacryloylethyltrimethylammonium chloride polymers, from the viewpoint of easily making the viscosity of a 1% by mass aqueous solution at 30°C or more a specific value, improving the texture improvement effect of the treated object and the sustainability of the effect, improving the tangling suppression effect of hair or fibers for hair accessories when used for hair or fibers for hair accessories and the sustainability of the effect, improving moisture resistance, and improving the stability of the composition. -Methoxy polyethylene glycol methacrylate copolymer (Polyquaternium-49), methacryloyl ethyl dimethyl betaine-methacryloyl ethyl trimethyl ammonium chloride-2-hydroxyethyl methacrylate copolymer (Polyquaternium-48), and N,N-dimethylaminoethyl methacrylate diethyl sulfate-N,N-dimethylacrylamide-dimethacrylate polyethylene glycol copolymer (Polyquaternium-52) One or more, more preferably methacryloyl ethyl trimethyl ammonium chloride polymer (Polyquaternium-37) and N,N-dimethylaminoethyl methacrylate diethyl sulfate-N,N-dimethylacrylamide-dimethacrylate polyethylene glycol copolymer (Polyquaternium-52) One or more.
[0054] As component (A), commercially available polymers may also be used. Specific examples thereof include "Cosmedia Ultragel 300" (polyquaternium-37, cationic charge density: 4.81 mmol / g) manufactured by BASF JAPAN Ltd., "Sofcare KG-101W-E" (polyquaternium-52, cationic charge density: 0.83 mmol / g), and "Sofcare KG-301W" (polyquaternium-52, cationic charge density: 1.84 mmol / g) manufactured by Kao Co., Ltd.
[0055] (Component (B): anionic polymer)
[0056] Component (B) is a polymer that can form a polyion complex by interaction with component (A). In this specification, "anionic polymer" refers to a polymer having anionic groups and substantially no cationic groups and amphoteric groups. "Substantially no cationic groups and amphoteric groups" means that the molar amount of cationic groups and amphoteric groups relative to anionic groups is preferably less than 0.1%.
[0057] As the anionic group possessed by component (B), preferably an acidic group such as a carboxyl group, a sulfonic acid group, a phosphoric acid group, etc., from the viewpoint of easily forming a polyion complex through interaction with component (A) and the viewpoint of availability, a carboxyl group is more preferred. Furthermore, in component (B), at least a part of the anionic group may also be neutralized to form a salt state.
[0058] <Component (B1): Crosslinked polymer containing a structural unit derived from (meth)acrylic acid, anionic polysaccharide>
[0059] From the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, improving moisture resistance, and improving the stability of the composition, component (B) preferably contains (B1) at least one selected from a cross-linked polymer containing a structural unit derived from (meth)acrylic acid and anionic polysaccharides.
[0060] In component (B1), as a cross-linked polymer containing a structural unit derived from (meth) acrylic acid, a homopolymer or copolymer of (meth) acrylic acid having a cross-linked structure, or a salt thereof can be cited. The cross-linked structure referred to herein refers to a three-dimensional network structure formed by polymer chains as the main structure of the polymer being linked within or between polymer chains. The method for forming the cross-linked structure is not particularly limited, and for example, it can be formed by a method of cross-linking simultaneously with polymerization such as polycondensation or free radical polymerization, or by a method of cross-linking the polymer chains after polymerization.
[0061] Examples of the homopolymer of (meth)acrylic acid include polyacrylic acid, polymethacrylic acid, and salts thereof.
[0062] Examples of the above-mentioned (meth)acrylic acid copolymers include (meth)acrylic acid / maleic acid copolymers, (meth)acrylic acid / itaconic acid copolymers, (meth)acrylic acid / fumaric acid copolymers, (meth)acrylic acid / vinyl acetate copolymers, (meth)acrylic acid / (meth)acrylic acid alkyl ester copolymers, (meth)acrylic acid / 2-hydroxyethyl methacrylate copolymers, acrylic acid / alkyl acrylate / (N-alkyl)acrylamide copolymers, and salts thereof. One or more of these can be used.
[0063] Among the above, the copolymer of (meth)acrylic acid is preferably (meth)acrylic acid / alkyl (meth)acrylate, and more preferably acrylic acid / alkyl acrylate. As the alkyl (meth)acrylate, there can be mentioned alkyl (meth)acrylates having an alkyl group with preferably 1 or more carbon atoms, more preferably 4 or more carbon atoms, further preferably 8 or more carbon atoms, and preferably 40 or less carbon atoms, more preferably 36 or less carbon atoms, further preferably 32 or less carbon atoms.
[0064] Specific examples of the cross-linked polymer containing a structural unit derived from (meth)acrylic acid include carboxyvinyl polymer or its salt, (acrylate / alkyl (C10-30) acrylate) cross-linked polymer, (sodium acrylate / acryloyldimethyl taurine / dimethyl acrylamide) cross-linked polymer, acrylate cross-linked polymer-4, etc.
[0065] Among component (B1), examples of anionic polysaccharides include polysaccharides having a carboxyl group (hyaluronic acid, alginic acid, pectinic acid, carboxymethyl cellulose, xanthan gum, etc.), sulfates of polysaccharides (carrageenan, keratan sulfate, dermatan sulfate, sulfated starch, heparin, heparan sulfate), and salts thereof, and one or more of these can be used.
[0066] Among the above, from the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, and improving the tangling-inhibiting effect of hair or fibers for hair ornament products and the sustainability of the effect when used for treating hair or fibers for hair ornament products, the anionic polysaccharide is preferably a polysaccharide having a carboxyl group or a salt thereof, more preferably alginic acid, carboxymethyl cellulose or a salt thereof, and still more preferably alginic acid or a salt thereof.
[0067] When the component (B1) is a salt, examples of the salt include alkali metal salts such as sodium salts and potassium salts, and alkaline earth metal salts. From the viewpoint of availability, alkali metal salts are preferred.
[0068] Among the above, from the viewpoints of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the fibers for hair or hair ornament products and the sustainability of the effect when used for treating the fibers for hair or hair ornament products, improving the moisture resistance, and improving the stability of the composition, component (B1) is preferably one or more selected from carboxyvinyl polymers, (acrylate / alkyl (C10-30) acrylate) crosslinked polymers, and anionic polysaccharides, more preferably anionic polysaccharides or salts thereof, and even more preferably alginic acid or salts thereof.
[0069] The anionic charge density of component (B1) is not particularly limited, but is preferably 1.0 mmol / g or more, more preferably 2.0 mmol / g or more, and further preferably 3.5 mmol / g or more, from the viewpoint of easily forming a polyion complex by interaction with component (A), improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of hair or fibers for hair ornament products when used for treating hair or fibers for hair ornament products and the sustainability of the effect, improving moisture resistance, and improving the stability of the composition. From the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of hair or fibers for hair ornament products when used for treating hair or fibers for hair ornament products and the sustainability of the effect, it is preferably 25 mmol / g or less, more preferably 20 mmol / g or less, and further preferably 15 mmol / g or less. The anion charge density of component (B1) is preferably from 1.0 mmol / g to 25 mmol / g, more preferably from 2.0 mmol / g to 20 mmol / g, and even more preferably from 3.5 mmol / g to 15 mmol / g.
[0070] The anionic charge density of component (B1) is the number of moles of anionic groups contained per 1 g of polymer. Furthermore, when at least a portion of the anionic groups of component (B1) are in the form of neutralized salts, the number of moles of anionic groups also includes the number of moles of anionic groups in the form of salts.
[0071] Two or more polymers may be used as the component (B1). In this case, the anionic charge density of the component (B1) is determined by calculating a weighted average from the anionic charge densities and blending amounts of the respective polymers.
[0072] When component (B1) is an anionic polysaccharide, from the viewpoint of improving film-forming ability, the weight average molecular weight (Mw) is preferably 2,000 or more, more preferably 10,000 or more, further preferably more than 30,000, and further more preferably 50,000 or more. In addition, from the viewpoint of easily forming a polyion complex by interaction with component (A), improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, improving moisture resistance, and improving the stability of the composition, it is preferably 3.5 million or less, and more preferably 3 million or less. The weight average molecular weight (Mw) of the anionic polysaccharide as component (B1) is preferably 2,000 to 3,500,000, more preferably 10,000 to 3,000,000, further preferably more than 30,000 to 3,000,000, and still more preferably 50,000 to 3,000,000.
[0073] The weight average molecular weight of the component (B1) can be measured by gel permeation chromatography (GPC).
[0074] The content of component (B1) in component (B) is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, further preferably 80% by mass or more, and is 100% by mass or less, from the viewpoints of improving the film-forming ability, facilitating the formation of a polyion complex by interaction with component (A), improving the texture-improving effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of hair or fibers for hair ornament products when used for treating hair or fibers for hair ornament products and the sustainability of the effect, improving moisture resistance, and improving the stability of the composition.
[0075] <Component (B2): Anionic polymer other than component (B1)>
[0076] From the viewpoint of further improving the texture-enhancing effect of the treated object and the sustainability of the effect, from the viewpoint of improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, and from the viewpoint of improving moisture resistance, component (B) preferably further contains (B2) an anionic polymer other than the above-mentioned component (B1).
[0077] When the composition of the present invention further contains the following (G) nonionic polymer, it is believed that component (B2) can be hydrogen-bonded with the (G) nonionic polymer to immobilize component (G) in the cross-linked structure of the polyion complex formed by component (A)-component (B). It is believed that due to this effect, even if the object is treated with the composition of the present invention and then rinsed or washed, component (G) will not be rinsed away and will easily remain in the membrane, thereby improving the sustainability of the treatment effect.
[0078] The molecular weight of component (B2) is preferably 1,000 or more, more preferably 2,000 or more, further preferably 5,000 or more, and further preferably 10,000 or more, and is preferably 50,000 or less, more preferably 40,000 or less, and further preferably 30,000 or less, from the viewpoint of facilitating the fixation of component (G), further improving the texture-enhancing effect of the treated object and the sustainability of the effect, particularly when used for treating hair or hair ornament fibers and the sustainability of the effect, and improving moisture resistance. Furthermore, the molecular weight of component (B2) is preferably 1,000 or more and 50,000 or less, more preferably 1,000 or more and 30,000 or less, further preferably 2,000 or more and 30,000 or less, further more preferably 5,000 or more and 30,000 or less, and further more preferably 10,000 or more and 30,000 or less.
[0079] The "molecular weight" referred to herein refers to a weight average molecular weight, which can be measured by gel permeation chromatography (GPC).
[0080] Component (B2) is preferably a polymer having a carboxyl group having a molecular weight of 1,000 to 50,000, more preferably 1,000 to 30,000, and more preferably a non-crosslinked polymer having a molecular weight of 1,000 to 30,000 containing a structural unit derived from (meth)acrylic acid.
[0081] Examples of the non-crosslinked polymer containing a structural unit derived from (meth)acrylic acid that is suitable for use as component (B2) include, in addition to poly(meth)acrylic acid, (meth)acrylic acid / maleic acid copolymers, (meth)acrylic acid / itaconic acid copolymers, (meth)acrylic acid / fumaric acid copolymers, (meth)acrylic acid / vinyl acetate copolymers, (meth)acrylic acid / alkyl (meth)acrylate copolymers, (meth)acrylic acid / 2-hydroxyethyl methacrylate copolymers, acrylic acid / alkyl acrylate / (N-alkyl)acrylamide copolymers, and salts thereof. One or more of these can be used.
[0082] Examples of the polymer having a carboxyl group other than the above that can be preferably used as the component (B2) include polymaleic acid, maleic acid / diisobutylene copolymers, maleic acid / styrene copolymers, benzoic acid formaldehyde condensates, benzoic acid / phenol / formaldehyde condensates, and salts thereof.
[0083] Among the above, from the viewpoint of further improving the texture-enhancing effect of the treated object and the sustainability of the effect, from the viewpoint of improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, and from the viewpoint of improving moisture resistance, component (B2) is preferably at least one selected from poly(meth)acrylic acid, (meth)acrylic acid / alkyl (meth)acrylate copolymers, and salts thereof.
[0084] Examples of the poly(meth)acrylic acid or a salt thereof include polyacrylic acid, polymethacrylic acid, and salts thereof, and polyacrylic acid or a salt thereof is preferred.
[0085] As the (meth)acrylic acid / (meth)acrylic acid alkyl ester copolymer or its salt, acrylic acid / acrylic acid alkyl ester or its salt is more preferred. As the (meth)acrylic acid alkyl ester, there can be mentioned alkyl (meth)acrylic acid esters in which the number of carbon atoms in the alkyl group is preferably 1 or more, more preferably 4 or more, further preferably 8 or more, further more preferably 12 or more, and preferably 40 or less, more preferably 36 or less, further preferably 32 or less, further more preferably 24 or less.
[0086] The (meth)acrylic acid / (meth)acrylic acid alkyl ester is preferably acrylic acid / alkyl acrylate, more preferably one or more selected from (acrylic acid / octyl acrylate) copolymer and (acrylic acid / stearyl acrylate) copolymer, and still more preferably (acrylic acid / stearyl acrylate) copolymer.
[0087] When the component (B2) is a salt, examples of the salt include alkali metal salts such as sodium salts and potassium salts, and alkaline earth metal salts. From the viewpoint of availability, alkali metal salts are preferred.
[0088] The anionic charge density of component (B2) is not particularly limited, but is preferably 1.0 mmol / g or more, more preferably 3.0 mmol / g or more, and more preferably 5.0 mmol / g or more, and preferably 25 mmol / g or less, more preferably 20 mmol / g or less, and more preferably 15 mmol / g or less, from the viewpoint of further improving the texture improvement effect of the treated object and the sustainability of the effect, improving the tangling inhibition effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and its sustainability, and improving moisture resistance. In addition, the anionic charge density of component (B2) is preferably 1.0 mmol / g or more and 25 mmol / g or less, more preferably 3.0 mmol / g or more and 20 mmol / g or less, and more preferably 5.0 mmol / g or more and 15 mmol / g or less.
[0089] Two or more polymers may be used as the component (B2). In this case, the anionic charge density of the component (B2) is determined by calculating a weighted average from the anionic charge densities and blending amounts of the respective polymers.
[0090] When component (B) contains component (B2), the content of component (B2) in component (B) is preferably 1% by mass or more, more preferably 2% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, from the viewpoint of further improving the texture-enhancing effect of the treated object and the sustainability of the effect, especially improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, and improving moisture resistance. From the viewpoint of the ease of forming a polyion complex with component (A), it is preferably 50% by mass or less, more preferably 40% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less. Furthermore, the content of component (B2) in component (B) is preferably 1% by mass or more and 50% by mass or less, more preferably 2% by mass or more and 40% by mass or less, more preferably 3% by mass or more and 30% by mass or less, and even more preferably 5% by mass or more and 20% by mass or less.
[0091] In addition, when the component (B) contains the component (B1) and the component (B2), the mass ratio of the component (B2) to the total amount of the component (B1) and the component (B2) [(B2) / {(B1)+(B2)}] is preferably 0.01 or more, more preferably 0.02 or more, further preferably 0.05 or more, and further preferably 0.08 or more, from the viewpoint of further improving the texture-enhancing effect of the treated object and the sustainability of the effect, especially improving the tangling-inhibiting effect of the fibers for hair or hair ornament products when used for treating the fibers for hair or hair ornament products and the sustainability of the effect, and improving the moisture resistance. From the viewpoint of the ease of forming a polyion complex with the component (A), it is preferably 1.0 or less, more preferably 0.80 or less, further preferably 0.50 or less, and further preferably 0.30 or less. The mass ratio [(B2) / {(B1)+(B2)}] is preferably 0.01 to 1.0, more preferably 0.02 to 0.80, further preferably 0.05 to 0.50, and still further preferably 0.08 to 0.30.
[0092] (Component (C): modified silicone)
[0093] Component (C) is one or more modified silicones selected from polyglycerol-modified silicones and amino-modified silicones. It is believed that the composition containing component (C) improves the texture of the treated object and the durability of the effect, especially the effect of inhibiting tangling of hair or hair ornament fibers when used for hair or hair ornament fiber treatment and its durability, and moisture resistance.
[0094] [Polyglycerol modified silicone]
[0095] The polyglycerol-modified silicone is a silicone having a polyglycerol chain in the molecule. The polyglycerol chain may be introduced at any position, and the introduction form may be any one of a single-end type, a double-end type, a side chain type, etc., but preferably, the silicone has a polyglycerol chain in the side chain or at the end of the silicone chain, and more preferably, the silicone has a monovalent polyglycerol group in the side chain or at the end of the silicone chain.
[0096] Specific examples of polyglyceryl-modified silicones include polyglyceryl-3 polydimethylsiloxyethyl dimethicone, polyglyceryl-3 dimethylsiloxy dimethicone, lauryl polyglyceryl-3 polydimethylsiloxyethyl dimethicone, cetyl diglyceryl-tris(trimethylsiloxy)silylethyl dimethicone, and bis(polyglyceryl-3-oxyphenylpropyl) dimethicone.
[0097] Examples of commercially available products of polyglycerol-modified silicone include “KF-6100,” “KF-6104,” “KF6106,” and “KF-6105” manufactured by Shin-Etsu Chemical Co., Ltd., “DOWSI ES-5600 Silicone Glycerol Emulsifier” manufactured by Dow Corning Co., Ltd., and “Sofcare GS-G” manufactured by Kao Corporation.
[0098] [Amino modified silicone]
[0099] Examples of amino-modified silicones include silicones having an amino group or an ammonium group-containing group in the main chain or side chain and having no polyether structure, such as dimethylpolysiloxane (polydimethylsiloxane) and methylphenylpolysiloxane. Preferably, silicones represented by the following general formula (2) are mentioned.
[0100]
[0101] [Where R 11 Each independently represents a methyl group or a phenyl group, and R 12 Each independently represents an alkyl group having 1 to 30 carbon atoms, a hydroxyl group or R 13 ; R 13 Indicates -R 14 -Z 1 (R 14 represents a single bond or a divalent hydrocarbon group having 1 to 20 carbon atoms, Z 1 represents a monovalent group represented by a group containing a primary to tertiary amino group or a group containing an ammonium group. a represents a number from 0 to 3000, b represents a number from 1 to 3000, and a+b is a number from 100 to 20,000.]
[0102] In the general formula (2), R 11 Preferably, methyl, R 12 Preferably methyl or R 13 .
[0103] R 13 For-R 14 -Z 1 The monovalent group represented by R 14 It is preferably a divalent hydrocarbon group having 1 to 20 carbon atoms, more preferably an alkylene group having 1 to 20 carbon atoms, further preferably a straight-chain or branched alkylene group having 1 to 6 carbon atoms, further more preferably a methylene group, an ethylene group, a trimethylene group, a propylene group, a tetramethylene group or a hexamethylene group, further more preferably a trimethylene group or a propylene group.
[0104] Z 1is a primary to tertiary amino group or an ammonium group, preferably -N(R 15 )2.-NR 15 (CH2) c N(R 16 )2 or -NR 15 (CH2) c N(R 16 )CO-R 17 The amino-containing group represented by + (R 15 )3A - 、-NR 15 (CH2) c N + (R 16 )3A - Here, R 15 and R 16 R each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and is preferably a hydrogen atom or a methyl group. 17 represents an alkyl group having 1 to 3 carbon atoms. A is an anion and represents Cl, Br or I. c represents a number of 1 to 6, preferably a number of 2 to 4.
[0105] In the general formula (2), R 13 Preferred are -(CH2)3-NH2, -(CH2)3-N(CH3)2, -(CH2)3-NH-(CH2)2-NH2 or -(CH2)2-NH-(CH2)2-N(CH3)2, more preferably -(CH2)3-NH2 or -(CH2)3-NH-(CH2)2-NH2.
[0106] Preferred silicones represented by the general formula (2) include at least one selected from aminoethylaminopropyl dimethicone [amodimethicone], aminopropyl dimethicone, bis(aminopropyl) dimethicone, and bis(cetyl) amodimethicone.
[0107] Commercial products of amino-modified silicone include "Silicone SF8457C" manufactured by Dow Toray Co., Ltd. Also, "DOWSIL CF 1046" manufactured by Dow Toray Co., Ltd., which is a mixture of amino-modified silicone and the following (D) dimethyl polysiloxane, may be used.
[0108] Component (C) may be used alone or in combination. Among the above, amino-modified silicone is preferred from the viewpoint of further improving the texture-enhancing effect of the treated object and the sustainability of the effect, and from the viewpoint of improving the tangling-inhibiting effect of hair or fibers for hair ornament products when used for treating hair or fibers for hair ornament products and the sustainability of the effect.
[0109] (ingredient (D): dimethyl polysiloxane)
[0110] Component (D) is dimethyl polysiloxane. It is believed that by including component (C) and component (D) in the composition of the present invention, the texture improvement effect of the treated object and the sustainability of the effect, especially the tangling suppression effect of hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, and moisture resistance are improved.
[0111] The dimethyl polysiloxane used as the component (D) preferably has low volatility. From this viewpoint, the viscosity at 25° C. is preferably 500 mm 2 / s or more, more preferably 700mm 2 / s or more, more preferably 1,000 mm 2 / s or more.
[0112] From the viewpoint of the effect of improving the texture of the treated object and the durability of the effect, especially the effect of inhibiting the tangling of hair or hair ornament fibers when used for treating hair or hair ornament fibers and the durability of the effect, and the improvement of moisture resistance, component (D) more preferably contains (D1) having a viscosity of 1,000 mm / s at 25°C. 2 / s above 10,000mm 2 / s or less dimethyl polysiloxane, and (D2) a viscosity of 300,000 mm at 25°C 2 / s above 5 million mm 2 / s or less dimethyl polysiloxane.
[0113] The viscosity of the component (D) is a value measured at 25° C. in accordance with “Methods for measuring viscosity of liquids” specified in JIS Z8803:2011 or ASTM D 445-46T, and can be measured using, for example, an Ubbelohde viscometer.
[0114] When component (D) contains component (D1) and component (D2), the mass ratio [(D1) / (D2)] of component (D1) to component (D2) is preferably 0.5 or more, more preferably 1.0 or more, and even more preferably 2.0 or more, and is preferably 20 or less, more preferably 10 or less, and even more preferably 5.0 or less, from the viewpoint of the effect of improving the texture of the treated object and the sustainability of the effect, especially the effect of inhibiting the tangling of hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, and the improvement of moisture resistance. Furthermore, the mass ratio [(D1) / (D2)] is preferably 0.5 or more and 20 or less, more preferably 1.0 or more and 10 or less, and even more preferably 2.0 or more and 5.0 or less.
[0115] When the component (D) contains the component (D1) and the component (D2), the total content of the component (D1) and the component (D2) in the component (D) is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, and is 100% by mass or less, from the viewpoint of further improving the texture-enhancing effect on the treated object and the sustainability of the effect, from the viewpoint of improving the tangling-inhibiting effect of the fibers for hair or hair ornament products when used for treating the fibers for hair or hair ornament products and the sustainability of the effect, and from the viewpoint of improving moisture resistance.
[0116] (Ingredient (E): cationic surfactant)
[0117] The composition of the present invention contains (E) a cationic surfactant from the viewpoint of further improving the touch of the object to be treated.
[0118] Examples of the cationic surfactant include (i) alkyltrimethylammonium salts, (ii) alkoxyalkyltrimethylammonium salts, (iii) dialkyldimethylammonium salts, (iv) alkylamidealkyltrimethylammonium salts, (v) alkyldimethylamines and salts thereof, (vi) alkoxyalkyldimethylamines and salts thereof, and (vii) alkylamidealkyldimethylamines and salts thereof.
[0119] As (i) the alkyltrimethylammonium salt, preferably, there can be mentioned an alkyltrimethylammonium salt having an alkyl group having 12 to 24 carbon atoms, more preferably 16 to 24 carbon atoms, and specifically, there can be mentioned cetyltrimethylammonium chloride (cetrimonium chloride), stearyltrimethylammonium chloride (octadecyltrimethylammonium chloride), behenyltrimethylammonium chloride (behenyltrimethylammonium chloride), and the like.
[0120] (ii) The alkoxyalkyltrimethylammonium salts include preferably alkoxyalkyltrimethylammonium salts having an alkoxy group having 12 to 22 carbon atoms, more preferably 16 to 20 carbon atoms, and specifically, stearoxypropyltrimethylammonium chloride, stearoxyethyltrimethylammonium chloride, stearoxyhydroxypropyltrimethylammonium chloride, and the like.
[0121] (iii) The dialkyldimethylammonium salt preferably includes a dialkyldimethylammonium salt having an alkyl group having 12 to 22 carbon atoms, more preferably 16 to 20 carbon atoms, and specifically, distearyldimethylammonium chloride and the like.
[0122] (iv) The alkylamide alkyltrimethylammonium salt preferably includes an alkylamide alkyltrimethylammonium salt having an alkyl group having 11 to 21 carbon atoms, more preferably 13 to 19 carbon atoms, and specifically includes palmitamide propyltrimethylammonium chloride (palmitamide propyltrimethylammonium chloride) and the like.
[0123] (v) Alkyldimethylamine, (vi) alkoxyalkyldimethylamine, and (vii) alkylamidealkyldimethylamine react with an acid to form a tertiary amine salt, thereby forming a cationic surfactant.
[0124] The alkyl group in (v) alkyldimethylamine and its salt, and the alkoxy group in (vi) alkoxyalkyldimethylamine and its salt are preferably an alkyl group having 12 to 22 carbon atoms, more preferably 16 to 20 carbon atoms.
[0125] (vii) Alkylamide The alkyl group of the alkylamide moiety in alkyldimethylamine and its salt is preferably an alkyl group having 11 to 21 carbon atoms, more preferably 15 to 19 carbon atoms.
[0126] The amines of (v) to (vii) may be reacted with an acid in advance and incorporated into the composition in the form of a salt. Alternatively, the amines may be incorporated into the composition directly in the form of an amine, and then an acid may be incorporated into the composition to form a salt. Therefore, the amines and their salts are defined as cationic surfactants herein. In addition, the content or amount thereof is converted to the mass of the amines.
[0127] As salts of the amines of (v) to (vii), salts formed by organic acids or inorganic acids can be cited. Examples of organic acids include monocarboxylic acids such as acetic acid and propionic acid; dicarboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, maleic acid, fumaric acid, and phthalic acid; polycarboxylic acids such as polyglutamic acid; hydroxycarboxylic acids such as glycolic acid, lactic acid, hydroxyacrylic acid, glyceric acid, malic acid, tartaric acid, and citric acid; acidic amino acids such as glutamic acid and aspartic acid. Examples of inorganic acids include hydrochloric acid, sulfuric acid, and phosphoric acid. Of these, organic acids are preferred, and more preferred are at least one selected from dicarboxylic acids, hydroxycarboxylic acids, and acidic amino acids. As dicarboxylic acids, more preferred are at least one selected from maleic acid and succinic acid. As hydroxycarboxylic acids, more preferred are at least one selected from glycolic acid, lactic acid, and malic acid. As acidic amino acids, more preferred are glutamic acid.
[0128] (v) Alkyldimethylamine and salts thereof include N,N-dimethylbehenylamine, N,N-dimethylstearylamine, and organic acid salts thereof, and lactic acid salts of N,N-dimethylbehenylamine and glycolic acid salts of N,N-dimethylstearylamine are preferred.
[0129] (vi) Alkoxyalkyldimethylamines and salts thereof include N,N-dimethyl-3-hexadecyloxypropylamine, N,N-dimethyl-3-octadecyloxypropylamine, and organic acid salts thereof, preferably N,N-dimethyl-3-hexadecyloxypropylamine or a lactate thereof, and N,N-dimethyl-3-octadecyloxypropylamine (stearyloxypropyldimethylamine) or a lactate thereof.
[0130] (vii) Alkylamide alkyldimethylamine and its salt include N-[3-(dimethylamino)propyl]behenamide, N-[3-(dimethylamino)propyl]stearamide, and organic acid salts thereof, preferably N-[3-(dimethylamino)propyl]behenamide lactate and N-[3-(dimethylamino)propyl]stearamide glycolate.
[0131] The component (E) can be used alone or in combination of two or more.
[0132] Among the above, from the viewpoint of further improving the touch of the treated object, component (E) is preferably one or more selected from (i) alkyltrimethylammonium salts, (ii) alkoxyalkyltrimethylammonium salts, (iii) dialkyldimethylammonium salts, (iv) alkylamidealkyltrimethylammonium salts, (v) alkyldimethylamines and their salts, (vi) alkoxyalkyldimethylamines and their salts, and (vii) alkylamidealkyldimethylamines and their salts, and more preferably one selected from (i) alkyltrimethylammonium salts and (vi) alkoxyalkyldimethylamines. The present invention further preferably comprises at least one selected from cetyl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, behenyl trimethyl ammonium chloride, N,N-dimethyl-3-hexadecyloxypropylamine or its lactate, and N,N-dimethyl-3-octadecyloxypropylamine (stearyloxypropyl dimethylamine) or its lactate, and further preferably comprises at least one selected from behenyl trimethyl ammonium chloride and N,N-dimethyl-3-octadecyloxypropylamine (stearyloxypropyl dimethylamine) or its lactate.
[0133] (Component (F): higher alcohol)
[0134] The composition of the present invention contains (F) a higher alcohol from the viewpoint of further improving the touch of the object to be treated.
[0135] Examples of the higher alcohol include aliphatic monohydric alcohols having 12 or more carbon atoms, preferably 12 or more and 22 or less carbon atoms. Examples of the higher alcohol include at least one selected from lauryl alcohol, cetyl alcohol, myristyl alcohol, oleyl alcohol, stearyl alcohol, isostearyl alcohol, 2-octyldodecanol, behenyl alcohol, and cetearyl alcohol.
[0136] Among the above, from the viewpoint of further improving the touch of the treated object, component (F) is preferably at least one selected from cetyl alcohol, myristyl alcohol, stearyl alcohol, and behenyl alcohol.
[0137] (Component (G): nonionic polymer)
[0138] From the viewpoint of further improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the knot-inhibiting effect of the fibers for hair or hair products and the sustainability of the effect, and improving the moisture resistance, the composition of the present invention preferably further contains (G) a nonionic polymer. It is believed that when component (G) is used, the rigid cross-linked structure of the polyion complex formed by component (A) and component (B) is enhanced by the composite with the long-chain and soft non-cross-linked structure of component (G). It is also believed that hydrogen bonding can be performed between component (B) and component (G), so that component (G) is maintained in the above-mentioned cross-linked structure by component (B), and a further high-strength mesh structure is formed in the film. As a result, it is believed that the texture-enhancing effect of the treated object and the sustainability and moisture resistance of the effect are further improved.
[0139] In the present specification, the "nonionic polymer" refers to a polymer that does not substantially have a cationic group, anionic group, or amphoteric group as an ionic group.
[0140] Component (G) includes polyalkylene glycol or derivatives thereof, polymers containing structural units derived from vinylpyrrolidone, polymers containing structural units derived from (meth)acrylate, polyvinyl alcohol, polyacrylamide, polycaprolactam, etc., and one or more of these can be used.
[0141] Examples of the polyalkylene glycol include homopolymers or copolymers of alkylene glycols in which the number of carbon atoms of the alkylene group is 2 to 6, preferably 2 to 4, and more preferably 2 to 3. Specific examples thereof include polyethylene glycol, polypropylene glycol, polytrimethylene ether glycol, polytetramethylene ether glycol, polyethylene glycol-polypropylene glycol copolymer (polyoxyethylene polyoxypropylene glycol), polyethylene glycol-polytrimethylene ether glycol copolymer, polyethylene glycol-polytetramethylene ether glycol copolymer, polypropylene glycol-polytetramethylene ether glycol copolymer, and the like. Among these, from the viewpoints of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, improving moisture resistance, and availability, at least one selected from polyethylene glycol, polypropylene glycol, and polyethylene glycol-polypropylene glycol copolymers is preferred, and at least one selected from polyethylene glycol and polyethylene glycol-polypropylene glycol copolymers is more preferred.
[0142] Examples of the polyalkylene glycol derivatives include terminal modified products of the above-mentioned polyalkylene glycols, such as polyalkylene glycol monoalkyl ethers, polyalkylene glycol dialkyl ethers, polyalkylene glycol monoaryl ethers, polyalkylene glycol diaryl ethers, polyalkylene glycol monofatty acid esters, polyalkylene glycol difatty acid esters, polyalkylene glycol diglycidyl ethers, etc. Among these, from the viewpoints of improving the texture-improving effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of hair or fibers for hair ornament products when used for treating hair or fibers for hair ornament products and the sustainability of the effect, and from the viewpoint of availability, preferably at least one selected from polyalkylene glycol monoalkyl ethers, polyalkylene glycol dialkyl ethers, polyalkylene glycol monofatty acid esters, and polyalkylene glycol difatty acid esters, and more preferably at least one selected from polyalkylene glycol monofatty acid esters and polyalkylene glycol difatty acid esters.
[0143] The number of carbon atoms of the alkyl group in the mono- or di-alkyl ether of the polyalkylene glycol and the number of carbon atoms of the fatty acid in the mono- or di-fatty acid ester of the polyalkylene glycol are preferably 1 to 36, more preferably 4 to 32, further preferably 8 to 24, and further more preferably 12 to 22. In addition, the number of carbon atoms of the aryl group in the mono- or diaryl ether of the polyalkylene glycol is preferably 6 to 36, more preferably 6 to 32, further preferably 6 to 24, and further more preferably 6 to 22.
[0144] Specific examples of the polyalkylene glycol derivatives include polyethylene glycol monomethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol monobutyl ether, polyethylene glycol dibutyl ether, polyethylene glycol monooctyl ether, polyethylene glycol monodecyl ether, polyethylene glycol monododecyl ether, polyethylene glycol monotridecyl ether, polyethylene glycol-bisphenol A ether, polyethylene glycol dilaurate, polyethylene glycol distearate (polyethylene glycol distearate), polyethylene glycol diglycidyl ether, polyethylene glycol-polypropylene glycol-monomethyl ether, polyethylene glycol-polypropylene glycol-dimethyl ether. , polyethylene glycol-polypropylene glycol-monobutyl ether, polyethylene glycol-polypropylene glycol-dibutyl ether, polyethylene glycol-polypropylene glycol-monooctyl ether, polyethylene glycol-polypropylene glycol-monodecyl ether, polyethylene glycol-polypropylene glycol-monododecyl ether, polyethylene glycol-polypropylene glycol-monotridecyl ether, polyethylene glycol-polypropylene glycol-bisphenol A ether, polyethylene glycol-polypropylene glycol-dilaurate, polyethylene glycol-polypropylene glycol distearate, polyethylene glycol-polypropylene glycol-diglycidyl ether, etc., and one or more of these can be used.
[0145] Examples of polymers containing structural units derived from vinyl pyrrolidone include homopolymers of vinyl pyrrolidone and copolymers of vinyl pyrrolidone and nonionic monomers, and specific examples thereof include polyvinyl pyrrolidone, vinyl pyrrolidone / vinyl acetate copolymers, and vinyl pyrrolidone / methacrylamide / vinylimidazole copolymers.
[0146] Examples of the polymer containing a structural unit derived from (meth)acrylate include homopolymers of (meth)acrylate and copolymers of (meth)acrylate with nonionic monomers such as (meth)acrylamide, dimethylacrylamide, vinyl acetate, and vinyl methyl ether. Examples of (meth)acrylate include hydroxyalkyl (meth)acrylates, alkyl (meth)acrylates, and the like in addition to the above-mentioned alkyl (meth)acrylates.
[0147] Specific examples of the polymer containing a structural unit derived from a (meth)acrylate include a (dimethylacrylamide / hydroxyethyl acrylate / methoxyethyl acrylate) copolymer and a (hydroxyethyl acrylate / methoxyethyl acrylate) copolymer.
[0148] Among the above, from the viewpoints of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, improving moisture resistance, and availability, component (G) is preferably at least one selected from polyalkylene glycol or a derivative thereof, and a polymer containing a structural unit derived from vinyl pyrrolidone, more preferably at least one selected from polyethylene glycol, polypropylene glycol, a polyethylene glycol-polypropylene glycol copolymer, mono- or di-fatty acid esters thereof, and polyvinyl pyrrolidone, and still more preferably at least one selected from polyethylene glycol, a polyethylene glycol-polypropylene glycol copolymer, mono- or di-fatty acid esters thereof, and polyvinyl pyrrolidone.
[0149] From the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the fibers for hair or hair ornament products and the sustainability of the effect when used for treating the fibers for hair or hair ornament products, improving moisture resistance, and the viewpoint of availability, the weight average molecular weight (Mw) of the component (G) is preferably 2,000 or more, more preferably 5,000 or more, and even more preferably 10,000 or more, and preferably 2,000,000 or less, and even more preferably 1,500,000 or less. Furthermore, the weight average molecular weight of the component (G) is preferably 2,000 or more and 2,000,000 or less, more preferably 5,000 or more and 1,500,000 or less, and even more preferably 10,000 or more and 1,500,000 or less.
[0150] The weight average molecular weight of the component (G) can be measured by gel permeation chromatography (GPC).
[0151] (Component (H): acid)
[0152] From the viewpoint of stably forming a polyion complex, the composition of the present invention preferably further contains (H) an acid.
[0153] As component (H), an organic acid or an inorganic acid can be used, and from the viewpoint of use in a cosmetic composition or a fiber treatment composition for a headdress product, an organic acid is preferred. As the organic acid, carboxylic acid compounds and sulfonic acid compounds other than component (B) can be cited, preferably compounds having a molecular weight of 500 or less, more preferably 200 or less.
[0154] As carboxylic acid compounds, for example, there can be listed: aliphatic monocarboxylic acids having less than 4 carbon atoms, such as acetic acid, propionic acid, and butyric acid; aromatic monocarboxylic acids, such as benzoic acid; aliphatic dicarboxylic acids, such as malonic acid, succinic acid, glutaric acid, adipic acid, maleic acid, and fumaric acid; aromatic dicarboxylic acids, such as phthalic acid and isophthalic acid; polycarboxylic acids, such as polyglutamic acid; hydroxycarboxylic acids, such as lactic acid, malic acid, glycolic acid, hydroxyacrylic acid, glyceric acid, tartaric acid, and citric acid; acidic amino acids, such as glutamic acid and aspartic acid, etc., and one or more of these can be used.
[0155] Examples of the sulfonic acid compound include aliphatic sulfonic acids such as methanesulfonic acid and ethanesulfonic acid; and aromatic sulfonic acids such as p-toluenesulfonic acid and naphthalenesulfonic acid. One or more of these can be used.
[0156] From the viewpoint of stably forming a polyion complex to form a composition with higher stability, and from the viewpoint of being used in a cosmetic composition or a fiber treatment composition for a headdress product, the organic acid is preferably at least one selected from aliphatic dicarboxylic acids, hydroxycarboxylic acids, and aromatic sulfonic acids, more preferably at least one selected from succinic acid, lactic acid, malic acid, glycolic acid, p-toluenesulfonic acid, and naphthalenesulfonic acid, further preferably at least one selected from succinic acid and lactic acid, and further more preferably lactic acid.
[0157] Furthermore, when the organic acid is blended, at least a part of it may be in the form of an organic acid salt. As the salt of the organic acid, from the viewpoint of use in a cosmetic composition or a fiber treatment composition for a headdress product, and from the viewpoint of easy availability, an alkali metal salt or an alkali metal salt of the organic acid is preferred, an alkali metal salt is more preferred, and at least one selected from a sodium salt and a potassium salt is further preferred, and a sodium salt is further preferred.
[0158] From the viewpoint of the ease of formation of the polyion complex and the stability of the composition, the ratio of the organic acid salt in the total amount of the organic acid and the organic acid salt is preferably 50% by mass or less, more preferably 20% by mass or less, further preferably 5% by mass or less, and may be 0% by mass. The ratio (mass %) of the organic acid salt mentioned here refers to the mass % converted into the organic acid.
[0159] (water)
[0160] From the viewpoint of preparing an emulsified composition, the composition of the present invention preferably contains water. The water used in the composition of the present invention is preferably deionized water or distilled water. Furthermore, tap water, groundwater, etc. sterilized with hypochlorous acid or the like may also be used within the range that does not impair the stability of the composition.
[0161] (content)
[0162] From the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, improving moisture resistance, and improving the stability of the composition, the content or blending amount of each component in the composition of the present invention is preferably as follows.
[0163] From the viewpoint of the ease of forming a polyion complex, improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and its sustainability, and improving moisture resistance, the content of component (A) in the composition is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, further preferably 0.05% by mass or more, further more preferably 0.1% by mass or more, and further more preferably 0.2% by mass or more. In addition, from the viewpoint of improving the stability of the composition, it is preferably 3.0% by mass or less, more preferably 2.5% by mass or less, further preferably 2.0% by mass or less, further more preferably 1.5% by mass or less, and further more preferably 1.0% by mass or less. Furthermore, the content of component (A) in the composition is preferably from 0.01 mass % to 3.0 mass %, more preferably from 0.02 mass % to 2.5 mass %, further preferably from 0.05 mass % to 2.0 mass %, further more preferably from 0.1 mass % to 1.5 mass %, further more preferably from 0.2 mass % to 1.5 mass %, further more preferably from 0.2 mass % to 1.0 mass %.
[0164] From the viewpoint of the ease of forming a polyion complex, improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and its sustainability, and improving moisture resistance, the content of component (B) in the composition is preferably 0.005% by mass or more, more preferably 0.01% by mass or more, further preferably 0.02% by mass or more, and further more preferably 0.025% by mass or more. In addition, from the viewpoint of improving the stability of the composition, it is preferably 3.0% by mass or less, more preferably 2.0% by mass or less, further preferably 1.5% by mass or less, further more preferably 1.0% by mass or less, further more preferably 0.5% by mass or less, further more preferably 0.3% by mass or less, further more preferably 0.2% by mass or less, and further more preferably 0.1% by mass or less. Furthermore, the content of component (B) in the composition is preferably from 0.005 mass % to 3.0 mass %, more preferably from 0.01 mass % to 2.0 mass %, further preferably from 0.02 mass % to 1.5 mass %, further more preferably from 0.02 mass % to 1.0 mass %, further more preferably from 0.02 mass % to 0.5 mass %, further more preferably from 0.02 mass % to 0.3 mass %, further more preferably from 0.02 mass % to 0.3 mass %, further more preferably from 0.02 mass % to 0.2 mass %, further more preferably from 0.02 mass % to 0.1 mass %, further more preferably from 0.025 mass % to 0.1 mass %.
[0165] From the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and its sustainability, and improving moisture resistance, the total content of component (A) and component (B) in the composition is preferably 0.02% by mass or more, more preferably 0.04% by mass or more, further preferably 0.05% by mass or more, further more preferably 0.1% by mass or more, further more preferably 0.2% by mass or more, and further more preferably 0.3% by mass or more. In addition, from the viewpoint of improving the stability of the composition, it is preferably 5.0% by mass or less, more preferably 4.0% by mass or less, further preferably 3.0% by mass or less, and further more preferably 2.0% by mass or less. Furthermore, the total content of component (A) and component (B) in the composition is preferably from 0.02 mass % to 5.0 mass %, more preferably from 0.04 mass % to 4.0 mass %, further preferably from 0.05 mass % to 3.0 mass %, further more preferably from 0.1 mass % to 2.0 mass %, further more preferably from 0.2 mass % to 2.0 mass %, further more preferably from 0.3 mass % to 2.0 mass %.
[0166] Regarding the content ratio of component (A) and component (B) contained in the composition, from the viewpoint of the ease of forming a polyion complex, improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of hair or hair ornament fiber when used for hair or hair ornament fiber treatment and the sustainability of the effect, and improving moisture resistance, the mass ratio of component (A) to component (B) [(A) / (B)] is 4.5 or more, preferably 4.7 or more, more preferably 4.8 or more, further preferably 5.0 or more, further more preferably 5.5 or more, further more preferably 6.0 or more, further more preferably 6.2 or more, and further more preferably 6.5 or more. In addition, from the viewpoint of improving the stability of the composition, it is preferably 20 or less, more preferably 18 or less, further preferably 16 or less, and further more preferably 15 or less. Furthermore, the mass ratio [(A) / (B)] is 4.5 or more, preferably 4.5 or more and 20 or less, more preferably 4.7 or more and 18 or less, further preferably 4.8 or more and 18 or less, further preferably 5.0 or more and 18 or less, further more preferably 5.5 or more and 16 or less, further more preferably 6.0 or more and 16 or less, further more preferably 6.2 or more and 15 or less, further more preferably 6.5 or more and 15 or less.
[0167] In the composition of the present invention, the mass ratio of component (A) to component (B) and the cationic charge / anionic charge ratio of component (A) to component (B) more significantly contribute to the effect of the present invention.
[0168] From the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the fibers for hair or hair ornament products when used for treating hair or hair ornament products and the sustainability of the effect, and improving moisture resistance, the ratio of the number of moles of the cationic charge of the component (A) to the number of moles of the anionic charge of the component (B) in the composition (cationic charge of the component (A) / anionic charge of the component (B)) is preferably 10 / 90 to 95 / 5, more preferably 20 / 80 to 95 / 5, further preferably 25 / 75 to 90 / 10, further preferably 30 / 70 to 90 / 10, further more preferably 40 / 60 to 90 / 10, further more preferably 50 / 50 to 90 / 10, further more preferably 52 / 48 to 90 / 10.
[0169] From the viewpoint of improving the texture improvement effect of the object to be processed and the persistence of the effect, improving the knotting inhibition effect of the hair or hair ornament fiber used for hair or hair ornament fiber when being processed and its persistence, and improving the viewpoint of moisture resistance, the content of the component (C) in the composition is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, further preferably 0.05% by mass or more, and further more preferably 0.1% by mass or more. In addition, from the viewpoint of improving the stability of the composition, it is preferably 5.0% by mass or less, more preferably 3.0% by mass or less, and further preferably 2.0% by mass or less. And, the content of the component (C) in the composition is preferably 0.01% by mass or more and 5.0% by mass or less, more preferably 0.02% by mass or more and 3.0% by mass or less, further preferably 0.05% by mass or more and 2.0% by mass or less, and further more preferably 0.1% by mass or more and 2.0% by mass or less.
[0170] From the viewpoint of improving the texture improvement effect of the object to be treated and the persistence of the effect, improving the knotting inhibition effect of the hair when being treated with fibers for hair or headdress products and its persistence, and improving the viewpoint of moisture resistance, the content of the component (D) in the composition is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, further preferably 0.3% by mass or more, and further more preferably 0.5% by mass or more. In addition, from the viewpoint of improving the stability of the composition, it is preferably 15% by mass or less, more preferably 10% by mass or less, and further preferably 8.0% by mass or less. And, the content of the component (D) in the composition is preferably 0.05% by mass or less and 15% by mass or less, more preferably 0.1% by mass or less and 10% by mass or less, further preferably 0.3% by mass or less and 8.0% by mass or less, and further more preferably 0.5% by mass or less and 8.0% by mass or less.
[0171] From the viewpoint of improving the texture improvement effect of the object to be treated and the persistence of the effect, improving the knotting inhibition effect of the fiber for hair or hair ornament products when being treated with fibers for hair or hair ornament products and its persistence, and improving the viewpoint of moisture resistance, the total content of the components (C) and (D) in the composition is preferably 0.06% by mass or more, more preferably 0.1% by mass or more, further preferably 0.3% by mass or more, further more preferably 0.5% by mass or more, further more preferably 0.6% by mass or more. In addition, from the viewpoint of improving the stability of the composition, it is preferably 20% by mass or less, more preferably 15% by mass or less, further preferably 10% by mass or less. And, the total content of the components (C) and (D) in the composition is preferably 0.06% by mass or more and 20% by mass or less, more preferably 0.1% by mass or more and 15% by mass or less, further preferably 0.3% by mass or more and 10% by mass or less, further more preferably 0.5% by mass or more and 10% by mass or less, further more preferably 0.6% by mass or more and 10% by mass or less.
[0172] Regarding the content ratio of the component (C) and the component (D) in the composition, from the viewpoint of the easiness of forming a polyion complex, the improvement of the texture-enhancing effect of the treated object and the sustainability of the effect, the improvement of the tangling-inhibiting effect of the hair or hair ornament fiber when used for treating the hair or hair ornament fiber and the sustainability of the effect, and the improvement of moisture resistance, the mass ratio of the component (C) to the component (D) [(C) / (D)] is preferably 0.02 or more, more preferably 0.05 or more, and even more preferably 0.1 or more, and is preferably 20 or less, more preferably 10 or less, even more preferably 5.0 or less, even more preferably 2.0 or less, even more preferably 1.0 or less, and even more preferably 0.5 or less. Furthermore, the mass ratio [(C) / (D)] is preferably 0.02 to 20, more preferably 0.02 to 10, further preferably 0.05 to 5.0, further more preferably 0.05 to 2.0, further more preferably 0.1 to 1.0, further more preferably 0.1 to 0.5.
[0173] From the viewpoint of further improving the touch of the object to be treated, the content of the component (E) in the composition is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and more preferably 0.5% by mass or more. In addition, from the viewpoint of improving the stability of the composition, it is preferably 10% by mass or less, more preferably 5.0% by mass or less, and more preferably 3.5% by mass or less. In addition, the content of the component (E) in the composition is preferably 0.1% by mass or more and 10% by mass or less, more preferably 0.2% by mass or more and 5.0% by mass or less, and more preferably 0.5% by mass or more and 3.5% by mass or less.
[0174] From the viewpoint of further improving the feel of the object to be treated, the content of the component (F) in the composition is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, more preferably 0.5% by mass or more, and further more preferably 1.0% by mass or more. In addition, from the viewpoint of improving the stability of the composition, it is preferably 15% by mass or less, more preferably 12% by mass or less, and further preferably 10% by mass or less. In addition, the content of the component (F) in the composition is preferably 0.1% by mass or more and 15% by mass or less, more preferably 0.2% by mass or more and 12% by mass or less, further preferably 0.5% by mass or more and 12% by mass or less, and further more preferably 1.0% by mass or more and 10% by mass or less.
[0175] From the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and its sustainability, improving moisture resistance, and improving the stability of the composition, the total content of components (A) to (F) in the composition is preferably 1.0% by mass or more, more preferably 2.0% by mass or more, further preferably 3.0% by mass or more, and further more preferably 5.0% by mass or more. In addition, from the viewpoint of improving the stability of the composition, it is preferably 50% by mass or less, more preferably 40% by mass or less, further preferably 30% by mass or less, more preferably 25% by mass or less, and further preferably 21.5% by mass or less. Furthermore, the total content of components (A) to (F) in the composition is preferably from 1.0 mass % to 50 mass %, more preferably from 2.0 mass % to 40 mass %, further preferably from 3.0 mass % to 30 mass %, further more preferably from 5.0 mass % to 25 mass %, further more preferably from 5.0 mass % to 21.5 mass %.
[0176] When the composition contains the nonionic polymer (G), the content of the component (G) in the composition is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, further preferably 0.05% by mass or more, and further preferably 0.1% by mass or more, from the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, and improving the tangling-inhibiting effect of the hair or hair ornament fiber when used for hair or hair ornament fiber treatment and its sustainability, and from the viewpoint of improving moisture resistance. In addition, from the viewpoint of improving the stability of the composition, it is preferably 3.0% by mass or less, more preferably 2.5% by mass or less, further preferably 2.0% by mass or less, further more preferably 1.5% by mass or less, and further more preferably 1.0% by mass or less. Furthermore, the content of component (G) in the composition is preferably from 0.01 mass % to 3.0 mass %, more preferably from 0.02 mass % to 2.5 mass %, further preferably from 0.05 mass % to 2.0 mass %, further more preferably from 0.1 mass % to 1.5 mass %, further more preferably from 0.1 mass % to 1.0 mass %.
[0177] When the composition contains the (G) nonionic polymer, the mass ratio of the component (G) to the total amount of the component (A) and the component (B) in the composition [(G) / {(A)+(B)}] is preferably 0.2 or more, more preferably 0.3 or more, even more preferably 0.4 or more, even more preferably 0.5 or more, even more preferably 0.6 or more, even more preferably 0.8 or more, and is preferably 20 or less, more preferably 15 or less, even more preferably 10 or less, even more preferably 8.0 or less, even more preferably 5.0 or less, even more preferably 2.0 or less, even more preferably 1.5 or less, from the viewpoint of improving the texture-enhancing effect of the treated object and the sustainability of the effect, especially improving the tangling-inhibiting effect of the hair or hair ornament product fiber when used for hair or hair ornament product fiber treatment and the sustainability of the effect, and from the viewpoint of improving moisture resistance. Furthermore, the mass ratio [(G) / {(A)+(B)}] is preferably 0.2 to 20, more preferably 0.3 to 15, further preferably 0.4 to 10, further preferably 0.5 to 8.0, further more preferably 0.6 to 5.0, further more preferably 0.8 to 2.0, further more preferably 0.8 to 1.5.
[0178] When the composition contains (H) acid, from the viewpoint of easy formation of polyion complex, the content of component (H) in the composition is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, further preferably 0.03% by mass or more, further more preferably 0.05% by mass or more, further more preferably 0.1% by mass or more, further more preferably 0.2% by mass or more. In addition, from the viewpoint of easy formation of polyion complex and the viewpoint of improving the stability of the composition, it is preferably 5.0% by mass or less, more preferably 3.0% by mass or less, further preferably 2.5% by mass or less. Furthermore, the content of component (H) in the composition is preferably from 0.01 mass % to 5.0 mass %, more preferably from 0.02 mass % to 3.0 mass %, further preferably from 0.03 mass % to 3.0 mass %, further more preferably from 0.05 mass % to 3.0 mass %, further more preferably from 0.05 mass % to 3.0 mass %, further more preferably from 0.1 mass % to 3.0 mass %, further more preferably from 0.1 mass % to 2.5 mass %, further more preferably from 0.2 mass % to 2.5 mass %.
[0179] In addition, when the organic acid is blended in the state of an organic acid salt, the above content is the amount converted into the organic acid.
[0180] However, when the composition contains any one of (v) alkyldimethylamine and salts thereof, (vi) alkoxyalkyldimethylamine and salts thereof, and (vii) alkylamidealkyldimethylamine and salts thereof as component (E), the content of component (H) in the composition may be an amount exceeding 5.0% by mass. This is because component (H) exists as a counter anion of the above amines, and thus, it is expected that the stability of the composition will be improved.
[0181] When the composition contains water, from the viewpoint of the ease of formation of the polyion complex and the viewpoint of improving the stability of the composition, the content of water in the composition is preferably 10% by mass or more, more preferably 20% by mass or more, and further preferably 30% by mass or more. In addition, from the viewpoint of improving the stability of the composition and the viewpoint of the degree of freedom of coordination, it is preferably 99% by mass or less, more preferably 95% by mass or less, and further preferably 90% by mass or less. In addition, the content of water in the composition is preferably 10% by mass or more and 99% by mass or less, more preferably 20% by mass or more and 95% by mass or less, and further preferably 30% by mass or more and 90% by mass or less. The content of water in the composition may also be the remainder of components (A) to (F).
[0182] (Other ingredients)
[0183] The composition of the present invention may contain anionic surfactants, nonionic surfactants, amphoteric surfactants, aromatic ring-containing alcohols such as benzyl alcohol and phenoxyethanol, non-aromatic polyols such as dipropylene glycol, oils other than components (C), (D), and (F), antioxidants, antidandruff agents, vitamins, bactericides, anti-inflammatory agents, preservatives, chelating agents, moisturizers, pearlescent agents, ceramides, fragrances, plant extracts, ultraviolet absorbers, pH adjusters, and the like as optional ingredients.
[0184] (pH value)
[0185] From the viewpoint of safety, the pH of the composition is preferably 3.0 or more, more preferably 3.2 or more, as measured by the pH of an aqueous solution obtained by diluting the composition 20 times with water at 25° C. From the viewpoint of improving the stability of the composition, it is preferably 7.5 or less, more preferably 7.0 or less, further preferably 6.0 or less, and further more preferably 5.0 or less.
[0186] The pH value can be measured using a pH meter by the method described in Examples.
[0187] (Method for producing composition)
[0188] The method for producing the composition is not particularly limited. When the composition is an emulsified composition, it is preferably produced by a method comprising the following steps 1 to 3, any one of steps 4-1 or 4-2, and step 5 in order from the viewpoint that a composition having a high texture-improving effect on a treated object and a long-lasting effect, particularly a high tangling-inhibiting effect on hair or fibers for hair ornament products when used for treating hair or fibers for hair ornament products and a long-lasting effect, an excellent moisture-resistant improving effect, and a high stability can be produced.
[0189] Step 1: a step of preparing a solution 1 containing (B) anionic polymer;
[0190] Step 2: a step of mixing the solution 1 with (H) an acid or an aqueous solution thereof to prepare a mixture 2 comprising (B) anionic polymer, (H) acid, and water;
[0191] Step 3: a step of mixing the mixture 2 and (A) a cationic polymer to prepare a mixture 3 comprising (A) a cationic polymer, (B) an anionic polymer, (H) an acid, and water;
[0192] Step 4-1: a step of mixing an aqueous phase (I) containing water and an oily phase (I) containing (D) a cationic surfactant and (E) a higher alcohol to prepare an emulsion (Ia), and then mixing the emulsion (Ia) with the mixture 3 to prepare an emulsion 4-1;
[0193] Step 4-2: a step of mixing the mixture 3 with an aqueous phase (I) containing water to prepare an aqueous phase (Ia), and then mixing the aqueous phase (Ia) with an oily phase (I) containing (D) a cationic surfactant and (E) a higher alcohol to prepare an emulsion 4-2;
[0194] Step 5: A step of mixing the emulsion 4-1 or 4-2 with an oily phase (II) containing (C) one or more modified silicones selected from polyglycerol-modified silicones and amino-modified silicones and (D) dimethyl polysiloxane.
[0195] According to the above method, the formation of the polyion complex is not hindered by other components, and the polyion complex can be formed efficiently. As a result, it is considered that a composition can be produced which has a high effect of improving the texture of the treated object and the durability of the effect, especially a high effect of inhibiting the tangling of hair or hair ornament fibers when used for treating hair or hair ornament fibers and the durability of the effect, an excellent effect of improving moisture resistance, and a high stability.
[0196] In the present specification, the “aqueous phase” refers to a phase constituting a water phase in the production process of an emulsified composition, and the “oil phase” refers to a phase constituting an oil phase in the production process of an emulsified composition.
[0197] In step 1, the solution 1 containing the anionic polymer (B) can be prepared by dissolving or dispersing the anionic polymer (B) in water. When preparing a solution in which the component (B) is dissolved or dispersed in water, the component (B) may be dispersed in an aqueous medium other than water such as dipropylene glycol before dissolving or dispersing in water.
[0198] As the solution formed by dissolving or dispersing component (B) in water, a commercially available aqueous solution or aqueous dispersion can also be used. In addition, for example, the reaction solution when using water as the reaction solvent to manufacture component (B) can also be used as the solution formed by dissolving or dispersing component (B) in water.
[0199] In step 3, the cationic polymer (A) may be directly mixed with the mixture 2. However, from the viewpoint of ease of production, it is preferred that a solution prepared by dissolving or dispersing the component (A) in water is mixed with the mixture 2.
[0200] As the solution formed by dissolving or dispersing component (A) in water, a commercially available aqueous solution or aqueous dispersion can also be used. In addition, for example, the reaction solution when using water as a reaction solvent to manufacture component (A) can also be used as the solution formed by dissolving or dispersing component (A) in water.
[0201] When the above-mentioned (G) nonionic polymer is used, it is preferred that in the above-mentioned step 1, a solution obtained by dissolving or dispersing the (B) anionic polymer in water is mixed with the (G) nonionic polymer to prepare a solution 1 containing the (B) anionic polymer and the (G) nonionic polymer, and the solution 1 is supplied to the steps 2 and below.
[0202] Regarding the above-mentioned embodiment, the present invention further discloses the following.
[0203] <1>
[0204] A cosmetic composition or a fiber treatment composition for a headdress product, comprising: (A) a cationic polymer having a viscosity of 1,000 mPa·s or more in a 1 mass % aqueous solution at 30° C., (B) an anionic polymer, (C) one or more modified silicones selected from polyglycerol-modified silicone and amino-modified silicone, (D) dimethyl polysiloxane, (E) a cationic surfactant, and (F) a higher alcohol, wherein the mass ratio of the component (A) to the component (B) [(A) / (B)] is 4.5 or more.
[0205] <2>
[0206] The composition as described in <1>, wherein the viscosity of a 1 mass % aqueous solution of the component (A) at 30°C is 1,000 mPa·s or more, preferably 1,000 mPa·s or more and 100,000 mPa·s or less, more preferably 1,300 mPa·s or more and 80,000 mPa·s or less, further preferably 1,500 mPa·s or more and 50,000 mPa·s or less, further more preferably 1,700 mPa·s or more and 30,000 mPa·s or less, and further more preferably 1,800 mPa·s or more and 25,000 mPa·s or less.
[0207] <3>
[0208] The composition as described in <1> or <2>, wherein the cationic charge density of the component (A) is preferably from 0.1 mmol / g to 20 mmol / g, more preferably from 0.2 mmol / g to 15 mmol / g, from 0.2 mmol / g to 12 mmol / g, further more preferably from 0.3 mmol / g to 10 mmol / g, further more preferably from 0.3 mmol / g to 7.0 mmol / g, further more preferably from 0.5 mmol / g to 5.0 mmol / g.
[0209] <4>
[0210] The composition as described in any one of <1> to <3>, wherein the component (A) is one or more selected from the group consisting of cationized polyvinyl alcohol, polyethylene imine, methacryloylethyltrimethylammonium salt polymer, quaternized dialkylaminoalkyl (meth)acrylate polymer, diallyl quaternary ammonium salt polymer, methacrylamidepropyltrimethylammonium salt polymer, vinylimidazolium trichloride-vinyl pyrrolidone copolymer (polyquaternium-16), vinyl pyrrolidone-alkylamino (meth)acrylate copolymer, vinyl pyrrolidone-alkylamino (meth)acrylate-vinyl caprolactam copolymer, alkyl acrylamide-(meth)acrylate-alkylaminoalkyl acrylamide-polyethylene glycol (meth)acrylate copolymer, and adipic acid-dimethylaminohydroxypropylethylenetriamine copolymer.
[0211] <5>
[0212] The composition according to any one of <1> to <4>, wherein the component (A) is a polymer containing a structural unit represented by the following general formula (1).
[0213]
[0214] In formula (1), R 1 is a hydrogen atom or a methyl group, R2 ~R 4 Each independently represents an alkyl group having 1 to 4 carbon atoms. X represents -O- or -NH-, and m represents a number of 1 to 4.
[0215] <6>
[0216] The composition as described in <6>, wherein the content of the structural unit represented by the general formula (1) in the component (A) is preferably 8.0 mol% or more, more preferably 10 mol% or more and 100 mol% or less, based on all the structural units constituting the component (A).
[0217] <7>
[0218] The composition as described in any one of <1> to <6>, wherein the component (A) is preferably one or more selected from methacryloylethyltrimethylammonium salt polymers and quaternized dialkylaminoalkyl (meth)acrylate polymers, and more preferably selected from methacryloylethyltrimethylammonium chloride polymers (polyquaternium-37), methacryloylethyldimethylbetaine-methacryloylethyltrimethylammonium chloride-methoxypolyethylene glycol methacrylate copolymer (polyquaternium-49), methacryloylethyldimethylbetaine-methacryloylethyltrimethylammonium chloride-methoxypolyethylene glycol methacrylate copolymer (polyquaternium-50), methacryloylethyltrimethylammonium chloride-methoxypolyethylene glycol methacrylate copolymer (polyquaternium-60), methacryloylethyltrimethylammonium chloride-methoxypolyethylene glycol methacrylate copolymer (polyquaternium-70), methacryloylethyltrimethylammonium chloride-methoxypolyethylene glycol methacrylate copolymer (polyquaternium-80), methacryloylethyltrimethylammonium chloride-methoxypolyethylene glycol methacrylate copolymer (polyquaternium-90), methacryloylethyltrimethylammonium chloride-methacryloylethyltrimethylammonium chloride-methoxypolyethylene glycol methacrylate copolymer (polyquaternium-10 ... Ammonium chloride-2-hydroxyethyl methacrylate copolymer (Polyquaternium-48), and N,N-dimethylaminoethyl methacrylate diethyl sulfate-N,N-dimethylacrylamide-dimethacrylate polyethylene glycol copolymer (Polyquaternium-52) are preferably one or more, and methacryloylethyltrimethylammonium chloride polymer (Polyquaternium-37) and N,N-dimethylaminoethyl methacrylate diethyl sulfate-N,N-dimethylacrylamide-dimethacrylate polyethylene glycol copolymer (Polyquaternium-52) are more preferably one or more.
[0219] <8>
[0220] The composition according to any one of <1> to <7>, wherein the component (B) contains (B1) one or more selected from a cross-linked polymer containing a structural unit derived from (meth)acrylic acid and anionic polysaccharides.
[0221] <9>
[0222] The composition according to <8>, wherein the cross-linked polymer including a structural unit derived from (meth)acrylic acid is a homopolymer or copolymer of (meth)acrylic acid having a cross-linked structure, or a salt thereof.
[0223] <10>
[0224] The composition according to <10>, wherein the homopolymer of (meth)acrylic acid is one or more selected from the group consisting of polyacrylic acid, polymethacrylic acid, and salts thereof.
[0225] <11>
[0226] The composition as described in <10>, wherein the copolymer of (meth)acrylic acid is at least one selected from (meth)acrylic acid / maleic acid copolymers, (meth)acrylic acid / itaconic acid copolymers, (meth)acrylic acid / fumaric acid copolymers, (meth)acrylic acid / vinyl acetate copolymers, (meth)acrylic acid / alkyl (meth)acrylate copolymers, (meth)acrylic acid / 2-hydroxyethyl methacrylate copolymers, acrylic acid / alkyl acrylate / (N-alkyl)acrylamide copolymers, and salts thereof, preferably (meth)acrylic acid / alkyl (meth)acrylate, and more preferably acrylic acid / alkyl acrylate.
[0227] <12>
[0228] The composition as described in any one of <8> to <11>, wherein the cross-linked polymer containing a structural unit derived from (meth)acrylic acid is one or more selected from carboxyvinyl polymer or its salt, (acrylate / alkyl acrylate (C10-30) ester) cross-linked polymer, (sodium acrylate / acryloyldimethyl taurine / dimethyl acrylamide) cross-linked polymer, and acrylate cross-linked polymer-4.
[0229] <13>
[0230] A composition as described in any one of <8> to <12>, wherein the anionic polysaccharide is one or more selected from polysaccharides having a carboxyl group, sulfates of polysaccharides, and salts thereof, preferably a polysaccharide having a carboxyl group or a salt thereof, more preferably alginic acid, carboxymethyl cellulose or a salt thereof, further preferably alginic acid or a salt thereof.
[0231] <14>
[0232] A composition as described in any one of <8> to <13>, wherein the component (B1) is preferably one or more selected from carboxyvinyl polymers, (acrylate / alkyl acrylate (C10-30) ester) cross-linked polymers, and anionic polysaccharides, more preferably anionic polysaccharides or salts thereof, and further preferably alginic acid or salts thereof.
[0233] <15>
[0234] The composition as described in any one of <8> to <14>, wherein the anion charge density of the component (B1) is preferably from 1.0 mmol / g to 25 mmol / g, more preferably from 2.0 mmol / g to 20 mmol / g, and further preferably from 3.5 mmol / g to 15 mmol / g.
[0235] <16>
[0236] The composition as described in any one of <8> to <15>, wherein the weight average molecular weight (Mw) of the anionic polysaccharide as the component (B1) is preferably from 2,000 to 3,500,000, more preferably from 10,000 to 3,000,000, further preferably from 30,000 to 3,000,000, and further more preferably from 50,000 to 3,000,000.
[0237] <17>
[0238] The composition as described in any one of <8> to <16>, wherein the content of the component (B1) in the component (B) is preferably 50 mass % or more, more preferably 60 mass % or more, further preferably 70 mass % or more, further more preferably 80 mass % or more, and is 100 mass % or less.
[0239] <18>
[0240] The composition according to any one of <8> to <17>, wherein the component (B) further comprises (B2) an anionic polymer other than the component (B1).
[0241] <19>
[0242] The composition as described in <18>, wherein the molecular weight of the component (B2) is preferably 1,000 to 50,000, more preferably 1,000 to 30,000, further preferably 2,000 to 30,000, further more preferably 5,000 to 30,000, further more preferably 10,000 to 30,000.
[0243] <20>
[0244] The composition as described in <18> or <19>, wherein the component (B2) is preferably a polymer having a carboxyl group and having a molecular weight of 1,000 to 50,000, more preferably 1,000 to 30,000, and more preferably a non-crosslinked polymer having a molecular weight of 1,000 to 30,000 containing a structural unit derived from (meth)acrylic acid.
[0245] <21>
[0246] The composition as described in <20>, wherein the non-crosslinked polymer containing a structural unit derived from (meth)acrylic acid is one or more selected from poly(meth)acrylic acid, (meth)acrylic acid / maleic acid copolymer, (meth)acrylic acid / itaconic acid copolymer, (meth)acrylic acid / fumaric acid copolymer, (meth)acrylic acid / vinyl acetate copolymer, (meth)acrylic acid / (meth)acrylic acid alkyl ester copolymer, (meth)acrylic acid / 2-hydroxyethyl methacrylate copolymer, acrylic acid / alkyl acrylate / (N-alkyl)acrylamide copolymer, and salts thereof.
[0247] <22>
[0248] The composition according to any one of <18> to <21>, wherein the component (B2) is one or more selected from poly(meth)acrylic acid, (meth)acrylic acid / alkyl (meth)acrylate copolymers, and salts thereof.
[0249] <23>
[0250] The composition as described in any one of <18> to <22>, wherein the anion charge density of the component (B2) is preferably from 1.0 mmol / g to 25 mmol / g, more preferably from 3.0 mmol / g to 20 mmol / g, and further preferably from 5.0 mmol / g to 15 mmol / g.
[0251] <24>
[0252] A composition as described in any one of <18> to <23>, wherein the content of the component (B2) in the component (B) is preferably from 1 mass % to 50 mass %, more preferably from 2 mass % to 40 mass %, further preferably from 3 mass % to 30 mass %, and further more preferably from 5 mass % to 20 mass %.
[0253] <25>
[0254] A composition as described in any one of <18> to <24>, wherein the mass ratio of the component (B2) to the total amount of the component (B1) and the component (B2) [(B2) / {(B1)+(B2)}] is preferably from 0.01 to 1.0, more preferably from 0.02 to 0.80, further preferably from 0.05 to 0.50, and further more preferably from 0.08 to 0.30.
[0255] <26>
[0256] The composition as described in any one of <1> to <25>, wherein the polyglyceryl-modified silicone preferably has a polyglycerol chain on the side chain or at the end of the silicone chain, more preferably is a silicone having a monovalent polyglyceryl group on the side chain or at the end of the silicone chain, and further preferably is at least one selected from polyglyceryl-3 polydimethylsiloxyethyl polydimethicone, polyglyceryl-3 dimethylsiloxy polydimethicone, lauryl polyglyceryl-3 polydimethylsiloxyethyl polydimethicone, cetyl diglyceryl tris(trimethylsiloxy)silylethyl polydimethicone, and bis(polyglyceryl-3-oxyphenylpropyl) polydimethicone.
[0257] <27>
[0258] The composition according to any one of <1> to <26>, wherein the amino-modified silicone is a silicone represented by the following general formula (2).
[0259]
[0260] [Where R 11 Each independently represents a methyl group or a phenyl group, and R 12 Each independently represents an alkyl group having 1 to 30 carbon atoms, a hydroxyl group or R 13 . R 13 Indicates -R 14 -Z 1 (R 14 represents a single bond or a divalent hydrocarbon group having 1 to 20 carbon atoms, Z 1 represents a monovalent group represented by a group containing a primary to tertiary amino group or a group containing an ammonium group. a represents a number from 0 to 3000, b represents a number from 1 to 3000, and a+b is a number from 100 to 20,000.]
[0261] <28>
[0262] The composition as described in <27>, wherein the silicone represented by the general formula (2) is one or more selected from aminoethylaminopropyl polydimethylsiloxane [aminodimethicone], aminopropyl polydimethylsiloxane, bis(aminopropyl) polydimethylsiloxane, and bis(cetyl)amino polydimethylsiloxane.
[0263] <29>
[0264] The composition according to any one of <1> to <28>, wherein the component (C) is amino-modified silicone.
[0265] <30>
[0266] The composition according to any one of <1> to <29>, wherein the viscosity of the component (D) at 25° C. is preferably 500 mm 2 / s or more, more preferably 700mm 2 / s or more, more preferably 1,000 mm 2 / s or more.
[0267] <31>
[0268] The composition according to any one of <1> to <30>, wherein the component (D) comprises (D1) a viscosity of 1,000 mm at 25°C. 2 / s above 10,000mm 2 / s or less dimethyl polysiloxane, and (D2) a viscosity of 300,000 mm at 25°C 2 / s above 5 million mm 2 / s or less dimethyl polysiloxane.
[0269] <32>
[0270] The composition according to <31>, wherein the mass ratio of the component (D1) to the component (D2) [(D1) / (D2)] is preferably 0.5 to 20, more preferably 1.0 to 10, and even more preferably 2.0 to 5.0.
[0271] <33>
[0272] A composition as described in <31> or <32>, wherein the total content of the component (D1) and the component (D2) in the component (D) is preferably 50 mass % or more, more preferably 60 mass % or more, further preferably 70 mass % or more, further more preferably 80 mass % or more, further more preferably 90 mass % or more, and is 100 mass % or less.
[0273] <34>
[0274] The composition according to any one of <1> to <33>, wherein the component (E) is preferably at least one selected from (i) alkyltrimethylammonium salts, (ii) alkoxyalkyltrimethylammonium salts, (iii) dialkyldimethylammonium salts, (iv) alkylamidealkyltrimethylammonium salts, (v) alkyldimethylamines and salts thereof, (vi) alkoxyalkyldimethylamines and salts thereof, and (vii) alkylamidealkyldimethylamines and salts thereof, and more preferably at least one selected from (i) alkyltrimethylammonium salts and (vi) alkoxyalkyldimethyl The present invention further preferably comprises at least one selected from cetyl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, behenyl trimethyl ammonium chloride, N,N-dimethyl-3-hexadecyloxypropylamine or its lactate, and N,N-dimethyl-3-octadecyloxypropylamine (stearyloxypropyl dimethylamine) or its lactate, and further preferably comprises at least one selected from behenyl trimethyl ammonium chloride and N,N-dimethyl-3-octadecyloxypropylamine (stearyloxypropyl dimethylamine) or its lactate.
[0275] <35>
[0276] A composition as described in any one of <1> to <34>, wherein the component (F) is one or more selected from lauryl alcohol, cetyl alcohol, myristyl alcohol, oleyl alcohol, stearyl alcohol, isostearyl alcohol, 2-octyldodecanol, behenyl alcohol, and cetearyl alcohol, preferably one or more selected from cetyl alcohol, myristyl alcohol, stearyl alcohol, and behenyl alcohol.
[0277] <36>
[0278] The composition according to any one of <1> to <35>, further comprising (G) a nonionic polymer.
[0279] <37>
[0280] The composition as described in <36>, wherein the component (G) is one or more selected from polyalkylene glycol or a derivative thereof, a polymer containing a structural unit derived from vinyl pyrrolidone, a polymer containing a structural unit derived from (meth)acrylate, polyvinyl alcohol, polyacrylamide, and polycaprolactam.
[0281] <38>
[0282] The composition according to <37>, wherein the polyalkylene glycol is preferably at least one selected from polyethylene glycol, polypropylene glycol, and a polyethylene glycol-polypropylene glycol copolymer, and more preferably at least one selected from polyethylene glycol and a polyethylene glycol-polypropylene glycol copolymer.
[0283] <39>
[0284] A composition as described in <37>, wherein the polyalkylene glycol derivative is one or more selected from polyalkylene glycol monoalkyl ether, polyalkylene glycol dialkyl ether, polyalkylene glycol monoaryl ether, polyalkylene glycol diaryl ether, polyalkylene glycol monofatty acid ester, polyalkylene glycol difatty acid ester, and polyalkylene glycol diglycidyl ether, preferably one or more selected from polyalkylene glycol monoalkyl ether, polyalkylene glycol dialkyl ether, polyalkylene glycol monofatty acid ester, and polyalkylene glycol difatty acid ester, and more preferably one or more selected from polyalkylene glycol monofatty acid ester and polyalkylene glycol difatty acid ester.
[0285] <40>
[0286] A composition as described in any one of <36> to <39>, wherein the component (G) is preferably one or more selected from polyalkylene glycol or its derivatives, and a polymer comprising a structural unit derived from vinyl pyrrolidone, more preferably one or more selected from polyethylene glycol, polypropylene glycol, polyethylene glycol-polypropylene glycol copolymer, mono- or di-fatty acid esters thereof, and polyvinyl pyrrolidone, further preferably one or more selected from polyethylene glycol, polyethylene glycol-polypropylene glycol copolymer, mono- or di-fatty acid esters thereof, and polyvinyl pyrrolidone.
[0287] <41>
[0288] The composition according to any one of <36> to <40>, wherein the weight average molecular weight of the component (G) is preferably 2,000 to 2,000,000, more preferably 5,000 to 1,500,000, and even more preferably 10,000 to 1,500,000.
[0289] <42>
[0290] The composition according to any one of <1> to <41>, further comprising (H) an acid.
[0291] <43>
[0292] The composition according to <42>, wherein the component (H) is preferably an organic acid, and more preferably at least one selected from carboxylic acid compounds and sulfonic acid compounds other than the component (B).
[0293] <44>
[0294] A composition as described in <43>, wherein the organic acid is preferably at least one selected from aliphatic dicarboxylic acids, hydroxycarboxylic acids, and aromatic sulfonic acids, more preferably at least one selected from succinic acid, lactic acid, malic acid, glycolic acid, p-toluenesulfonic acid, and naphthalenesulfonic acid, further preferably at least one selected from succinic acid and lactic acid, and further more preferably lactic acid.
[0295] <45>
[0296] The composition according to any one of <1> to <44>, further comprising water.
[0297] <46>
[0298] A composition as described in any one of <1> to <45>, wherein the content of the component (A) in the composition is preferably 0.01 mass % to 3.0 mass %, more preferably 0.02 mass % to 2.5 mass %, further preferably 0.05 mass % to 2.0 mass %, further more preferably 0.1 mass % to 1.5 mass %, further more preferably 0.2 mass % to 1.5 mass %, further more preferably 0.2 mass % to 1.0 mass %.
[0299] <47>
[0300] The composition as described in any one of <1> to <46>, wherein the content of the component (B) in the composition is preferably 0.005 mass % to 3.0 mass %, more preferably 0.01 mass % to 2.0 mass %, further preferably 0.02 mass % to 1.5 mass %, further more preferably 0.02 mass % to 1.0 mass %, further more preferably 0.02 mass % to 0.5 mass %, further more preferably 0.02 mass % to 0.3 mass %, further more preferably 0.02 mass % to 0.3 mass %, further more preferably 0.02 mass % to 0.2 mass %, further more preferably 0.02 mass % to 0.1 mass %, further more preferably 0.025 mass % to 0.1 mass %.
[0301] <48>
[0302] A composition as described in any one of <1> to <47>, wherein the total content of the component (A) and the component (B) in the composition is preferably 0.02 mass % to 5.0 mass %, more preferably 0.04 mass % to 4.0 mass %, further preferably 0.05 mass % to 3.0 mass %, further more preferably 0.1 mass % to 2.0 mass %, further more preferably 0.2 mass % to 2.0 mass %, further more preferably 0.3 mass % to 2.0 mass %.
[0303] <49>
[0304] A composition as described in any one of <1> to <48>, wherein the mass ratio of the component (A) to the component (B) contained in the composition [(A) / (B)] is preferably 4.5 or more and 20 or less, more preferably 4.7 or more and 18 or less, further preferably 4.8 or more and 18 or less, further preferably 5.0 or more and 18 or less, further more preferably 5.5 or more and 16 or less, further more preferably 6.0 or more and 16 or less, further more preferably 6.2 or more and 15 or less, further more preferably 6.5 or more and 15 or less.
[0305] <50>
[0306] A composition as described in any one of <1> to <49>, wherein the ratio of the molar number of cationic charge of the component (A) to the molar number of anionic charge of the component (B) in the composition (cationic charge of component (A) / anionic charge of component (B)) is preferably 10 / 90 to 95 / 5, more preferably 20 / 80 to 95 / 5, further preferably 25 / 75 to 90 / 10, further preferably 30 / 70 to 90 / 10, further more preferably 40 / 60 to 90 / 10, further more preferably 50 / 50 to 90 / 10, further more preferably 52 / 48 to 90 / 10.
[0307] <51>
[0308] The composition as described in any one of <1> to <50>, wherein the content of the component (C) in the composition is preferably from 0.01 mass % to 5.0 mass %, more preferably from 0.02 mass % to 3.0 mass %, further preferably from 0.05 mass % to 2.0 mass %, and even more preferably from 0.1 mass % to 2.0 mass %.
[0309] <52>
[0310] The composition as described in any one of <1> to <51>, wherein the content of the component (D) in the composition is preferably from 0.05 mass % to 15 mass %, more preferably from 0.1 mass % to 10 mass %, further preferably from 0.3 mass % to 8.0 mass %, and further more preferably from 0.5 mass % to 8.0 mass %.
[0311] <53>
[0312] A composition as described in any one of <1> to <52>, wherein the total content of the component (C) and the component (D) in the composition is preferably 0.06 mass % to 20 mass %, more preferably 0.1 mass % to 15 mass %, further preferably 0.3 mass % to 10 mass %, further more preferably 0.5 mass % to 10 mass %, further more preferably 0.6 mass % to 10 mass %.
[0313] <54>
[0314] A composition as described in any one of <1> to <53>, wherein the mass ratio of the component (C) to the component (D) in the composition [(C) / (D)] is preferably 0.02 to 20, more preferably 0.02 to 10, further preferably 0.05 to 5.0, further more preferably 0.05 to 2.0, further more preferably 0.1 to 1.0, further more preferably 0.1 to 0.5.
[0315] <55>
[0316] The composition as described in any one of <1> to <54>, wherein the content of the component (E) in the composition is preferably 0.1 mass % to 10 mass %, more preferably 0.2 mass % to 5.0 mass %, further preferably 0.5 mass % to 3.5 mass %.
[0317] <56>
[0318] A composition as described in any one of <1> to <55>, wherein the content of the component (F) in the composition is preferably from 0.1 mass % to 15 mass %, more preferably from 0.2 mass % to 12 mass %, further preferably from 0.5 mass % to 12 mass %, and further more preferably from 1.0 mass % to 10 mass %.
[0319] <57>
[0320] A composition as described in any one of <1> to <56>, wherein the total content of the components (A) to (F) in the composition is preferably from 1.0 mass % to 50 mass %, more preferably from 2.0 mass % to 40 mass %, further preferably from 3.0 mass % to 30 mass %, further more preferably from 5.0 mass % to 25 mass %, further more preferably from 5.0 mass % to 21.5 mass %.
[0321] <58>
[0322] A composition as described in any one of <36> to <57>, wherein the content of the component (G) in the composition is preferably 0.01 mass % to 3.0 mass %, more preferably 0.02 mass % to 2.5 mass %, further preferably 0.05 mass % to 2.0 mass %, further more preferably 0.1 mass % to 1.5 mass %, further more preferably 0.1 mass % to 1.0 mass %.
[0323] <59>
[0324] A composition as described in any one of <36> to <58>, wherein the mass ratio of the component (G) in the composition to the total amount of the component (A) and the component (B) [(G) / {(A)+(B)}] is preferably 0.2 to 20, more preferably 0.3 to 15, further preferably 0.4 to 10, further preferably 0.5 to 8.0, further more preferably 0.6 to 5.0, further more preferably 0.8 to 2.0, further more preferably 0.8 to 1.5.
[0325] <60>
[0326] A composition as described in any one of <42> to <59>, wherein the content of the component (H) in the composition is preferably 0.01 mass % to 5.0 mass %, more preferably 0.02 mass % to 3.0 mass %, further preferably 0.03 mass % to 3.0 mass %, further more preferably 0.05 mass % to 3.0 mass %, further more preferably 0.05 mass % to 3.0 mass %, further more preferably 0.1 mass % to 3.0 mass %, further more preferably 0.1 mass % to 2.5 mass %, further more preferably 0.2 mass % to 2.5 mass %.
[0327] <61>
[0328] The composition as described in any one of <45> to <60>, wherein the content of the water in the composition is preferably from 10 mass % to 99 mass %, more preferably from 20 mass % to 95 mass %, further preferably from 30 mass % to 90 mass %.
[0329] <62>
[0330] A composition as described in any one of <1> to <61>, wherein the pH value of the aqueous solution obtained by diluting the composition 20 times with water at 25°C is preferably 3.0 or more, more preferably 3.2 or more, preferably 7.5 or less, more preferably 7.0 or less, further preferably 6.0 or less, and further more preferably 5.0 or less.
[0331] <63>
[0332] The composition according to any one of <1> to <62>, wherein the cosmetic composition is preferably a cosmetic composition for keratin substances such as skin, hair, eyelashes, eyebrows, nails, etc., and more preferably a cosmetic composition for skin or hair.
[0333] <64>
[0334] The composition as described in <63>, wherein the product form of the skin cosmetic composition is a shower gel, a facial cleanser, a bath agent, a deodorant preparation, a makeup cosmetic, a sunscreen, a primer, an emulsion, a beauty serum, or a cream.
[0335] <65>
[0336] The composition according to <63>, wherein the product form of the hair cosmetic composition is a shampoo, a hair serum, a conditioner, a hair treatment agent, a hair fixative, a hair dye or a perm agent, preferably a hair conditioner, a hair treatment agent or a hair fixative.
[0337] <66>
[0338] The composition according to any one of <1> to <65>, wherein the composition is preferably in the form of an emulsified composition, and more preferably an oil-in-water emulsified composition.
[0339] <67>
[0340] A method for producing a cosmetic composition or a fiber treatment composition for a headdress product, comprising the following steps 1 to 3, any one of steps 4-1 or 4-2, and step 5 in order.
[0341] Step 1: a step of preparing a solution 1 containing (B) anionic polymer;
[0342] Step 2: a step of mixing the solution 1 with (H) an acid or an aqueous solution thereof to prepare a mixture 2 comprising (B) anionic polymer, (H) acid, and water;
[0343] Step 3: a step of mixing the mixture 2 with (A) a cationic polymer to prepare a mixture 3 comprising (A) a cationic polymer, (B) an anionic polymer, (H) an acid, and water;
[0344] Step 4-1: a step of mixing an aqueous phase (I) containing water and an oily phase (I) containing (D) a cationic surfactant and (E) a higher alcohol to prepare an emulsion (Ia), and then mixing the emulsion (Ia) with the mixture 3 to prepare an emulsion 4-1;
[0345] Step 4-2: a step of mixing the mixture 3 with an aqueous phase (I) containing water to prepare an aqueous phase (Ia), and then mixing the aqueous phase (Ia) with an oily phase (I) containing (D) a cationic surfactant and (E) a higher alcohol to prepare an emulsion 4-2;
[0346] Step 5: A step of mixing the emulsion 4-1 or the emulsion 4-2 with an oily phase (II) containing (C) one or more modified silicones selected from polyglycerol-modified silicones and amino-modified silicones and (D) dimethyl polysiloxane.
[0347] Example
[0348] Hereinafter, the present invention will be described by way of examples, but the present invention is not limited to the scope of the examples. In addition, each measurement and evaluation in the examples were performed by the following methods.
[0349] (Measurement of Viscosity of 1 Mass % Aqueous Solution of Cationic Polymer)
[0350] A 1 mass % aqueous solution of the cationic polymer (component (A) or component (A')) used in each example was prepared, and the viscosity of the aqueous solution at 30° C. was measured using a B-type viscometer (TV-20 manufactured by Toki Sangyo). In the present example, the cationic polymer other than component (A) is described as "component (A')".
[0351] (pH determination)
[0352] The conditioner of each example was diluted 20 times with water, and the pH value at 25° C. was measured using a pH meter (F-51 manufactured by Horiba, Ltd.).
[0353] (Measurement of combing strength after treatment with conditioner + 2 shampooing)
[0354] (1) Mix 7 mL of "Kao Foam Hair Bleach L" (Part 1) and 15 mL of "Kao Foam Hair Dye D" (Part 2) manufactured by Kao Corporation and apply to a 20 cm long, 30 g mass Japanese hair tress. After standing for 20 minutes, rinse thoroughly with warm water at 35 to 40°C (bleaching treatment). Repeat this bleaching treatment 4 times to prepare a damaged hair tress for evaluation. Wash the hair tress with a normal shampoo of the following composition and make it contain 15 g ± 0.5 g of water.
[0355] (2) Apply 1.5 mL of the conditioner of each example to the above-mentioned hydrated hair bundle, apply it by hand and leave it for 30 seconds, then rinse it with warm water at 35-40°C for 15 seconds. Then, rub the front and back of the hair bundle 20 times each within 30 seconds with 1 mL of the above-mentioned ordinary shampoo, and rinse it for 15 seconds.
[0356] (3) Apply 1 mL of the following ordinary conditioner, rub it with your hands for 30 seconds, and rinse for 15 seconds. Again, use 1 mL of the above ordinary shampoo to rub the front and back of the hair 20 times each within 30 seconds, and rinse for 15 seconds.
[0357] (4) After combing the hair bundle with a brush to completely untangle the knot, adjust the water content of the hair bundle after rinsing to 15g±0.5g. Place in a combing force measuring device ("KOT-0303" manufactured by Utsunomiya Seiki Co., Ltd.), let two brushes (Kao Lunette) pass through the uppermost part of the hair bundle, comb at a constant speed (60rpm), and measure the load (g) applied when the comb passes through the hair tip. Combing is performed 50 times, and the average value of the combing load at a total of 50 points is defined as the value of "combing force immediately after treatment". The smaller the combing force value, the better the result. The combing load of the damaged hair bundle (water content 15g±0.5g) that was not subjected to the above-mentioned (2) treatment was 2055g. If the combing force is 1900g or less, it is judged that the shampoo resistance is good.
[0358] [Composition of regular shampoo] * The amount of ingredients is the amount of active ingredients.
[0359]
[0360] (*1) 42.0% by mass based on "Emal E-27C" manufactured by Kao Corporation (active ingredient content 27% by mass)
[0361] (*2) Aminon C-11S (manufactured by Kao Corporation), active ingredient content 100% by mass
[0362] [Composition of regular conditioner] * The amount of ingredients is the amount of active ingredients.
[0363]
[0364] (*3) "Farmin DM-E80" manufactured by Kao Corporation, active ingredient content 90% by mass
[0365] (*4) "Kalcol 8098" manufactured by Kao Corporation, active ingredient content 100% by mass
[0366] (*5) "PURAC ULTRAPURE90" manufactured by PURAC Thailand Ltd., active ingredient content 90% by mass
[0367] (Measurement of combing strength after treatment with conditioner + 4 shampooing)
[0368] After performing (1) to (2) in the above-mentioned "Measurement of combing force after treatment with conditioner + 2 times of shampooing", (3) was performed 3 times, and then (4) was performed to measure the combing force.
[0369] (Emulsified state of conditioner after 2 days)
[0370] 1 g of the conditioner of each example was dropped onto a black plastic plate 2 days after formulation, and the appearance when traced 10 times with fingers and the touch when crushed with fingers were evaluated according to the following criteria.
[0371] A: Agglomerated particles cannot be identified, and the texture is smooth when crushed with fingers.
[0372] B: Agglomerated particles cannot be identified, but feel rough when crushed with fingers
[0373] C: Agglomerated particles can be identified and feel rough when crushed with fingers
[0374] D: Detached
[0375] (Wetness resistance of treated hair)
[0376] 7 mL of "Kao Bubble Hair Bleach L" (Part 1) and 15 mL of "Kao Bubble Hair Dye D" (Part 2) manufactured by Kao Corporation were mixed and applied to a 30 cm long, 20 g mass Japanese hair tress. After standing for 20 minutes, the tress was thoroughly rinsed with warm water at 35 to 40°C (bleaching treatment). This bleaching treatment was repeated 4 times to prepare a damaged hair tress for evaluation.
[0377] After washing the hair bundle with the above-mentioned ordinary shampoo, 1 mL of the conditioner of each example was applied for 30 seconds and left in this state for 1 minute, then rinsed with running water at 35 to 40° C. for 30 seconds and dried with a hair dryer until completely dry.
[0378] The dried hair was straightened 10 times with a hair straightener ("AHI-938" manufactured by Miki Electric Industry Co., Ltd.) set at 160°C while being combed, and a photo of the hair bundle just after being straightened was taken. Then, the straightened hair was hung and left to stand for 30 minutes in a high humidity environment of 35°C and 80%RH, and the photo was taken again. In the two photos, the hair bundle width was measured at a position 23.5 cm from the root of the hair bundle, and the change in the hair bundle width just after straightening and after being stored under high humidity was calculated according to the following formula.
[0379] Hair strand width change value = (hair strand width after storage at high humidity) / (hair strand width immediately after straightening)
[0380] When the value is 1.3 or more, the appearance also looks broad, and therefore, it is judged that the moisture resistance is low.
[0381] Examples 1 to 13, Comparative Examples 1 to 11 (Preparation and Evaluation of Hair Conditioners)
[0382] A hair conditioner was prepared by the following procedure using the respective components in the amounts described in the table.
[0383] An anionic polymer (component (B1) or component (B1) and component (B2)) pre-dispersed in dipropylene glycol was added to a 500 mL beaker containing water, and heated and stirred at 56° C. After confirming that the anionic polymer was completely dissolved, in Examples 2 to 9 and 12 to 13, a nonionic polymer (G) was further added and completely dissolved.
[0384] Next, add 90% lactic acid (57% of the total amount) and a cationic polymer (component (A) or component (A')). Furthermore, add an oily phase obtained by mixing (E) a cationic surfactant, (F) a higher alcohol, the remaining dipropylene glycol, and benzyl alcohol in advance and dissolving them at 85°C, and stir at 56°C for 10 minutes. After stirring for 10 minutes, stop heating and start air cooling. After air cooling, add the silicone (component (C) and component (D)) listed in the table and the remaining 90% lactic acid, and cool while stirring until the liquid temperature becomes 40°C or less to obtain 500 mL of a conditioner.
[0385] The obtained conditioner was used to evaluate the hair according to the above method. The results are shown in Tables 1 to 4.
[0386] [Table 1]
[0387]
[0388] [Table 2]
[0389]
[0390] [Table 3]
[0391]
[0392] [Table 4]
[0393]
[0394] The components described in the table are as follows: The blending amounts (mass %) described in the table are effective amounts of the components.
[0395] <Component (A): Cationic polymer>
[0396] *1 Polyquaternium-52 (N,N-dimethylaminoethyl diethyl methacrylate sulfate-N,N-dimethylacrylamide-polyethylene glycol dimethacrylate copolymer), "Sofcare KG-101W-E" manufactured by Kao Corporation
[0397] *2 Polyquaternium-52 (N,N-dimethylaminoethyl diethyl methacrylate sulfate-N,N-dimethylacrylamide-polyethylene glycol dimethacrylate copolymer), "Sofcare KG-301W" manufactured by Kao Corporation
[0398] *3 Polyquaternium-37 (methacryloylethyltrimethylammonium chloride polymer), "Cosmedia Ultragel 300" manufactured by BASF JAPAN Ltd.
[0399] <Component (A'): Cationic polymer other than component (A)>
[0400] *4 Polyquaternium-22 (dimethyldiallylammonium chloride-acrylic acid copolymer liquid), "Merquat 295" manufactured by Lubrizol Advanced Materials, Inc.
[0401] *5 Polyquaternium-55 (a polymer of a quaternary ammonium salt obtained by the reaction of vinyl pyrrolidone, dimethylaminopropyl methacrylamide, and methacrylamidopropyl lauryl dimethyl ammonium chloride), "Styleze W17" manufactured by Ashland Japan Ltd.
[0402] <Component (B1): Anionic polymer>
[0403] *6 Sodium alginate, "Kimica Algin I-3-150" manufactured by KIMICA Corporation
[0404] *7 Sodium alginate, "Kimica Algin IL-2" manufactured by KIMICA Corporation
[0405] <Component (B2): Anionic polymer>
[0406] *8 (Acrylic acid / stearyl acrylate) copolymer, "Sofcare SA-37W" manufactured by Kao Corporation
[0407] *9 Polyacrylic acid, "JURYMER AC-10L" manufactured by Toagosei Co., Ltd.
[0408] *10 Polyacrylic acid (Mw 25000), manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.
[0409] *11 Polyacrylic acid (Mw 5000), manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.
[0410] <Ingredient (C): Modified silicone>
[0411] *12 Amino-modified silicone, "Silicone SF 8457C" manufactured by Dow Toray Co., Ltd.
[0412] *13 Polyglycerol-modified silicone, "Sofcare GS-G" manufactured by Kao Corporation
[0413] <Component (C'): Modified silicone other than component (C)>
[0414] *14 Amino polyether modified silicone, "DOWSIL SILSTYLE 104" manufactured by Dow Toray Co., Ltd.
[0415] <Ingredient (D): dimethyl polysiloxane>
[0416] *15 Dimethyl polysiloxane, “Silicone KHS-3” manufactured by Shin-Etsu Chemical Co., Ltd.
[0417] <Ingredient (G): Nonionic polymer>
[0418] *16: Polyethylene glycol, "Blaunon PEG-20000S" manufactured by Aoki Oil & Fats Industries, Mw: 20,000
[0419] *17 Polyvinylpyrrolidone, "Luviskol K90" manufactured by BASF JAPAN Ltd., Mw: 1.2 million
[0420] <Ingredient (E): Cationic surfactant>
[0421] *18 Stearyloxypropyl dimethylamine, "Farmin DM-E80" manufactured by Kao Corporation
[0422] *19 Behenyltrimethylammonium chloride, "Quartamin 2285-E" manufactured by Kao Corporation
[0423] <Ingredient (F): Higher alcohol>
[0424] *20 Cetyl alcohol, "Kalcol 6870" manufactured by Kao Corporation
[0425] <Ingredient (H): Acid>
[0426] *21 90% lactic acid, "PURAC ULTRAPURE90" manufactured by PURAC Thailand Ltd.
[0427] <Other>
[0428] *22Dipropylene glycol, "DPG-RF" manufactured by ADEKA Corporation
[0429] As shown in Tables 1 to 4, it can be seen that the composition of the present example can improve the anti-tangling effect of hair and its sustainability when used for hair treatment, suppress the tangling of hair under high humidity conditions, and has high stability. In contrast, the cosmetic composition of the comparative example is inferior in terms of the anti-tangling effect of hair and its sustainability improvement effect, the anti-tangling effect of hair, and the stability.
[0430] Industrial Applicability
[0431] According to the present invention, there can be provided a cosmetic composition or a fiber treatment composition for hair products that can improve the texture-enhancing effect of a treated object and the sustainability of the effect, as well as moisture resistance, and, particularly when used for treating hair or fibers for hair products, can improve the tangling-inhibiting effect of hair or fibers for hair products and the sustainability of the effect, can suppress the tangling of hair under high humidity conditions, and has high stability.
Claims
1. A cosmetic composition or a fiber treatment composition for a headdress product, wherein: The invention comprises: (A) a cationic polymer having a viscosity of 1% by mass aqueous solution at 30°C of 1,000 mPa·s or more, (B) an anionic polymer, (C) one or more modified silicones selected from polyglycerol-modified silicone and amino-modified silicone, (D) dimethyl polysiloxane, (E) a cationic surfactant, and (F) a higher alcohol, wherein the mass ratio (A) / (B) of the component (A) to the component (B) is 4.5 or more.
2. The composition according to claim 1, wherein The component (A) is a polymer comprising a structural unit represented by the following general formula (1): In formula (1), R 1 is a hydrogen atom or a methyl group, R 2 ~R 4 Each independently represents an alkyl group having 1 to 4 carbon atoms; X represents -O- or -NH-, and m represents a number of 1 to 4.
3. The composition according to claim 1 or 2, wherein The component (B) contains (B1) at least one selected from a cross-linked polymer containing a structural unit derived from (meth)acrylic acid and anionic polysaccharides.
4. The composition according to claim 3, wherein The component (B1) is alginic acid or a salt thereof.
5. The composition according to any one of claims 1 to 4, wherein The component (D) comprises (D1) having a viscosity of 1,000 mm at 25°C. 2 / s above 10,000mm 2 / s or less dimethyl polysiloxane, and (D2) a viscosity of 300,000 mm at 25°C 2 / s above 5 million mm 2 / s or less dimethyl polysiloxane.
6. The composition according to any one of claims 1 to 5, wherein The component (A) is at least one selected from the group consisting of methacryloylethyltrimethylammonium chloride polymer and N,N-dimethylaminoethyl diethyl methacrylate sulfate-N,N-dimethylacrylamide-polyethylene glycol dimethacrylate copolymer.
7. The composition according to any one of claims 1 to 6, wherein It further contains (G) a nonionic polymer.
8. The composition according to any one of claims 3 to 7, wherein The component (B) further includes (B2) an anionic polymer other than the component (B1).
9. The composition of claim 8, wherein The component (B2) is a non-crosslinked polymer having a molecular weight of 1,000 to 30,000 and containing a structural unit derived from (meth)acrylic acid.
10. The composition according to any one of claims 1 to 9, wherein The mass ratio (A) / (B) of the component (A) to the component (B) contained in the composition is 20 or less.
Citation Information
Patent Citations
Keratin treating composition
JP1978139734A
Multidirectional input device
JP2005166333A
Composition for treating hair
JP2008297295A